Polymer material and production method of the same, gas-absorbing material, and gas-recovering apparatus

JP2025028892AActive Publication Date: 2025-03-05JCCL INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024198613
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-05-21
Filing Date
2024-11-13
Publication Date
2025-03-05
Estimated Expiration
2040-05-21

AI Technical Summary

Benefits of technology

【0007】 本発明のポリマー材料の製造方法によれば、ガス可逆吸収性能を有しながら低含水性のポリマー材料を製造することができ、製造されたポリマー材料は、ガス可逆吸収材料として効果的に用いることができる。本発明のガス吸収材料を用いたガス回収装置は、二酸化炭素等の酸性ガスや水蒸気等を効率よく回収することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025028892000012
    Figure 2025028892000012
  • Figure 2025028892000013
    Figure 2025028892000013
  • Figure 2025028892000014
    Figure 2025028892000014
Patent Text Reader

Abstract

To develop a low water content polymer material while having gas reversible absorption performance, and provide an efficient production method of the polymer material at the same time.SOLUTION: A polymer material is an amine-containing polymer material including a polymer of a monomer mixture comprising a monofunctional monomer, and more than 10 mol% and 30 mol% or less of a polyfunctional monomer. An efficient production method of the polymer material includes: a polymer synthesis process of polymerizing monomers in a reaction mixture containing a monofunctional monomer, a polyfunctional monomer, a solvent, and an initiator to synthesize a polymer; and an amine-impregnating process of impregnating the polymer with amine, where the total monomer concentration of the reaction mixture is 0.7 mol / L or more, and the percentage of the polyfunctional monomer in monomers contained in the reaction mixture is more than 10 mol% and 30 mol% or less, provided that the amine-impregnating process needs not be performed when the monofunctional monomer has an amino group.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polymeric material and a method for its manufacture. [Background technology]

[0002] In recent years, global warming caused by carbon dioxide emitted from facilities such as thermal power plants, steelworks, and cement factories, and environmental pollution caused by harmful gases such as hydrogen sulfide have become problems, and research and development into gas separation and recovery has been promoted to prevent the effects of these gases. Among these, there is research on gas absorbents and gas separators that utilize the reversible gas absorption ability of polymer particles synthesized by polymerizing monomers with amino groups and monomers with hydrophobic groups. For example, Patent Documents 1 and 2 disclose that 55 mol% of N-(dimethylaminopropyl) methacrylamide, 43 mol% of N-tert-butylacrylamide, and 2 mol% of N,N'-methylenebisacrylamide were dissolved in water to prepare a monomer mixture (total monomer concentration 0.312 mol / L), to which 2,2'-azobis(2-methylpropionamidine) dihydrochloride was added as an initiator, and the mixture was then freeze-dried to produce polymer particles. The produced polymer particles can be formed into a film by a method such as spray-coating the aqueous dispersion onto a porous body, and it is disclosed that the film obtained is useful as a reversible gas absorption material that absorbs carbon dioxide and then releases carbon dioxide by heating. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2016 / 024633 [Patent Document 2] International Publication No. 2017 / 146231 Summary of the Invention [Problem to be solved by the invention]

[0004] The present inventors have carried out investigations with the objective of developing a polymer material having reversible gas absorption performance and low water content, and at the same time, providing a method for efficiently producing this polymer material. [Means for solving the problem]

[0005] Specifically, the following solutions are provided:

[0006] [1] An amine-containing polymeric material comprising a polymer of a monomer mixture consisting of a monofunctional monomer and more than 10 mol % but not more than 30 mol % of a multifunctional monomer. [2] The polymer material according to [1], wherein the monofunctional monomer has an amino group. [3] The polymer material according to [1] or [2], wherein the polyfunctional monomer is N,N'-alkylenebis(meth)acrylamide. [4] The polymer material according to [1] or [2], wherein the polyfunctional monomer has an amino group. [5] The polymer material according to [1] or [2], wherein the polyfunctional monomer has a plurality of amino groups. [6] The polymer material according to any one of [1] to [5], wherein the polymer is a polymer polymerized using 2,2'-azobis(2-methylpropionitrile) as an initiator. [7] The polymer material according to any one of [1] to [6], wherein the polymer is polymerized in the presence of a surfactant. [8] The polymer material according to any one of [1] to [7], further comprising a surfactant. [9] The polymer material according to [7] or [8], wherein the surfactant is cetyltrimethylammonium bromide.

[10] The polymer material according to any one of [1] to [9], which is a pulverized product.

[11] The polymer material according to any one of [1] to

[10] , which is a filtrate.

[12] The polymer material according to any one of [1] to

[11] , which is a dry product.

[13] The polymer material according to any one of [1] to

[12] , wherein the polymer is a polymer polymerized using water and an alcohol as a solvent.

[14] The polymer material according to any one of [1] to

[13] , wherein the monomer mixture contains a monomer having a hydrophobic group.

[15] The polymer material according to any one of [1] to

[14] , which is a polymer material for gas absorption.

[16] The polymer material according to any one of [1] to

[15] , which is a polymer material for absorbing carbon dioxide gas.

[17] The polymer material according to any one of [1] to

[16] , which is capable of reversibly absorbing carbon dioxide gas.

[18] The polymer material according to any one of [1] to

[17] , wherein when 1 gram of dry polymer is immersed in water at 30° C. overnight, the water content of the polymer is 3 grams or less.

[19] A polymer synthesis step of synthesizing a polymer by polymerizing monomers in a reaction mixture including a monofunctional monomer, a polyfunctional monomer, a solvent, and an initiator; an amine impregnation step of impregnating the polymer with a treatment liquid containing an amine, the total monomer concentration of the reaction mixture is 0.7 mol / L or more; the proportion of the polyfunctional monomer in the monomers contained in the reaction mixture is 10 to 30 mol %, In the case where the monofunctional monomer has an amino group, the amine impregnation step does not need to be carried out.

[20] The method for producing a polymer material according to

[19] , wherein the monofunctional monomer has an amino group, and the amine impregnation step is performed.

[21] The method for producing a polymer material according to

[19] , wherein the monofunctional monomer has an amino group, and the amine impregnation step is not performed.

[22] The method for producing a polymer material according to any one of

[19] to

[21] , wherein the polyfunctional monomer is N,N'-alkylenebis(meth)acrylamide.

[23] The method for producing a polymer material according to any one of

[19] to

[21] , wherein the polyfunctional monomer has an amino group.

[24] The method for producing a polymer material according to any one of

[19] to

[21] , wherein the polyfunctional monomer has a plurality of amino groups.

[25] The method for producing a polymer material according to any one of

[19] to

[24] , wherein the initiator is 2,2'-azobis(2-methylpropionitrile).

[26] The method for producing a polymer material according to any one of

[19] to

[25] , wherein the reaction mixture contains a surfactant.

[27] The method for producing a polymer material according to

[26] , wherein the surfactant is cetyltrimethylammonium bromide.

[28] The method for producing a polymer material according to any one of

[19] to

[27] , further comprising pulverizing the polymer obtained in the polymer synthesis step.

[29] The method for producing a polymer material according to any one of

[19] to

[28] , further comprising filtering the polymer obtained in the polymer synthesis step.

[30] The method for producing a polymer material according to any one of

[19] to

[29] , further comprising drying the polymer obtained in the polymer synthesis step.

[31] The method for producing a polymer material according to any one of

[19] to

[30] , wherein water and an alcohol are used as the solvent.

[32] The method for producing a polymer material according to any one of

[19] to

[31] , wherein the reaction mixture contains a monomer having a hydrophobic group.

[33] The method for producing a polymer material according to

[32] , further comprising the steps of: prior to the polymer synthesis step, heating a mixture containing a monomer having an amino group, a polyfunctional monomer, and water, and then adding a monomer having a hydrophobic group to the mixture.

[34] The method for producing a polymer material according to

[33] , wherein the monomer having a hydrophobic group is added in the form of an alcohol solution.

[35] The method for producing a polymer material according to any one of

[32] to

[34] , wherein a total monomer concentration in the reaction mixture is 3 mol / L or less.

[36] A method for producing a polymer material for use as a gas absorbing material, comprising the steps of: (1) preparing a polymer material for use as a gas absorbing material; and (2) preparing a polymer material for use as a gas absorbing material.

[37] A method for producing a polymer material for absorbing carbon dioxide gas, comprising the steps of:

[19] -

[36] .

[38] A method for producing a polymer material according to any one of

[19] to

[36] , which is a method for producing a polymer material capable of reversibly absorbing carbon dioxide gas.

[39] The method for producing a polymer material according to

[38] , wherein the water content of the polymer is 3 grams or less when 1 gram of the dried polymer is immersed in water at 30°C overnight.

[40] A polymer material produced by the production method according to any one of

[19] to

[39] .

[41] A gas absorbing material containing the polymer material according to any one of [1] to

[18] and

[40] .

[42] The gas absorbing material according to

[41] , further comprising a thermoplastic resin.

[43] The gas absorbing material according to

[42] , wherein the thermoplastic resin is polyethylene.

[44] The gas absorbing material according to any one of

[41] to

[43] , further comprising a filler.

[45] The gas absorbing material according to

[44] , wherein the filler has gas adsorption ability.

[46] The gas absorbing material according to

[44] or

[45] , wherein the filler is a powder.

[47] The gas absorbing material according to any one of

[44] to

[46] , wherein the filler is a fine particle having a primary particle diameter of 1000 nm or less.

[48] ​​The gas absorbing material according to any one of

[44] to

[47] , wherein the fine particles have a water contact angle of 70° or more.

[49] The gas absorbing material according to any one of

[44] to

[48] , wherein the filler is carbon black.

[50] The gas absorbing material according to any one of

[44] to

[48] , wherein the filler is carbon black that has been treated to be water repellent.

[51] The gas absorbing material according to any one of

[44] to

[48] , wherein the filler is fumed silica.

[52] The gas absorbing material according to any one of

[44] to

[48] , wherein the filler is fumed silica that has been treated to be water repellent.

[53] The gas absorbing material according to any one of

[44] to

[48] , wherein the filler is a fluorinated resin powder.

[54] The gas absorbing material according to any one of

[44] to

[48] , wherein the filler is Teflon (registered trademark) powder.

[55] The gas absorbing material according to any one of

[44] to

[48] , wherein the filler is activated carbon or zeolite.

[56] The gas absorbing material according to any one of

[41] to

[55] , which is swollen with water.

[57] The gas absorbing material according to any one of

[41] to

[56] , which is hydrated with water vapor.

[58] A gas absorbing material according to

[57] , to which carbon dioxide gas or bicarbonate ions are added when water is added.

[59] A gas absorbing cartridge filled with the gas absorbing material according to any one of

[41] to

[58] .

[60] A gas supply device comprising the gas absorbing material according to any one of

[41] to

[58] .

[61] A gas recovery device comprising the gas absorbing material according to any one of

[41] to

[58] .

[62] The gas recovery apparatus according to

[61] , wherein after the gas is absorbed by the gas absorbing material, the gas is desorbed by increasing the temperature of the gas absorbing material.

[63] The gas recovery device according to

[61] , wherein the gas is absorbed and stored in the gas absorbing material, and then the partial pressure of the gas is reduced to desorb the gas.

[64] The gas recovery device according to

[61] , wherein after the gas is absorbed by the gas absorbing material, the gas is desorbed by passing water vapor through the gas absorbing material.

[65] The gas recovery device according to

[61] , wherein after the gas is absorbed by the gas absorbing material, the gas is desorbed by passing high-temperature water through the gas absorbing material.

[66] A gas recovery device according to any one of

[61] to

[65] , wherein when the gas is absorbed by the gas absorbent material, a rise in temperature of the gas absorbent material due to the heat of the gas absorption reaction is suppressed by evaporating moisture from the gas absorbent material.

[67] The gas recovery device according to any one of

[61] to

[66] , wherein, when the gas is absorbed by the gas absorbing material, the temperature of the gas absorbing material is lowered by passing a dry gas through the gas absorbing material.

[68] The gas recovery apparatus according to any one of

[61] to

[67] , wherein the gas is an acidic gas.

[69] The gas recovery device according to any one of

[61] to

[67] , wherein the gas is carbon dioxide gas.

[70] The gas recovery apparatus according to any one of

[61] to

[67] , wherein the gas is water vapor. Effect of the Invention

[0007] According to the method for producing a polymer material of the present invention, a polymer material having low water content while having reversible gas absorption performance can be produced, and the produced polymer material can be effectively used as a reversible gas absorption material. A gas recovery device using the gas absorption material of the present invention can efficiently recover acid gases such as carbon dioxide, water vapor, etc. [Brief description of the drawings]

[0008] [Figure 1] 1 is a schematic diagram showing a first embodiment of a gas recovery device of the present invention. [Diagram 2] FIG. 4 is a schematic diagram showing a second embodiment of a gas recovery device of the present invention. [Diagram 3] This shows the particle size distribution of a mixture of various polymer pulverized materials and RY300 (polymer material containing fine particles). [Figure 4] This is a graph showing the amount of CO2 absorbed during the absorption process and the amount of CO2 emitted during the emission process for a polymer pulverized at the 7th rin and a microparticle-containing polymer material containing RY300 (sample 18), and a polymer pulverized at the 7th rin (sample 19). [Diagram 5]This is a graph showing the amount of CO2 absorbed during the absorption process of a microparticle-containing polymer material (sample 18) containing amino group-containing polymer powder ground at the 7th minute and RY300, and a powder (sample 20) obtained by grinding a mixture of polymer powder ground at the 1.5th minute and RY300 in a bead mill. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present invention will be described in detail below. The following description of the constituent elements may be based on a representative embodiment or a specific example, but the present invention is not limited to such an embodiment. In this specification, a numerical range expressed using "~" means a range including the numerical values ​​before and after "~" as the lower and upper limits. In this specification, "(meth)acrylamide" means "acrylamide" and "methacrylamide", and "(meth)acrylate" means "acrylate" and "methacrylate".

[0010] <Polymer materials> The polymeric material can be, for example, an amine-containing polymeric material that includes a polymer of a monomer mixture consisting of a monofunctional monomer and greater than 10 mole % and up to 30 mole % of a multifunctional monomer. The proportion of the polyfunctional monomer in the monomer mixture may be greater than 10 mol % and not more than 30 mol %, and may also be 15 mol % or more and 30 mol % or less. For example, the polymer material can be appropriately crosslinked or polymerized under conditions that do not cause excessive swelling, and has a large amount of amines and can increase the reversible absorption amount of acidic gases such as carbon dioxide gas and water vapor while having low water content even after immersion in water. In addition, the material can reversibly absorb large amounts of acid gas even under high humidity conditions, and can be used for a long period of time at a high packing rate per unit volume without swelling due to excessive water absorption, even in high humidity environments. Furthermore, without excessive water content, it is possible to eliminate the need for extra energy for adjusting the temperature of water when dissipating gases such as carbon dioxide by temperature control such as heating. The polymeric material can be efficiently manufactured by the manufacturing method described below.

[0011] <Method of manufacturing polymer materials> A method for producing a polymer material includes, for example, a polymer synthesis step of synthesizing a polymer by polymerizing monomers in a reaction mixture containing a monofunctional monomer, a polyfunctional monomer, a solvent, and an initiator, and an amine impregnation step of impregnating the polymer with a treatment liquid containing an amine, in which the total monomer concentration of the reaction mixture is 0.7 mol / L or more, and the proportion of polyfunctional monomers among the monomers contained in the reaction mixture can be more than 10 mol % and 30 mol % or less. However, when the monofunctional monomer has an amino group, the above-mentioned amine impregnation step may not be carried out. In the method for producing a polymer material, by setting the total monomer concentration and the proportion of the polyfunctional monomer in the reaction mixture within the above ranges, a polymer material that has low water content but a large reversible gas absorption capacity can be efficiently obtained. Furthermore, a sufficient amount of polymer can be synthesized using a relatively small amount of solvent, which makes it possible to prevent the need for a large-scale production apparatus. Furthermore, since the obtained polymer material has low swelling properties, when it is commercialized as a gas absorbent or gas separating material, a sufficiently large volume filling rate can be achieved. Each step will be described in detail below.

[0012] [1] Polymer synthesis process In this process, a polymer is synthesized by polymerizing monomers in a reaction mixture containing a monofunctional monomer, a polyfunctional monomer, a solvent, and an initiator. The monomers, solvents, initiators, and surfactants used as necessary in the polymer synthesis process, as well as the polymerization reaction conditions and post-treatment of the polymer, will be described below.

[0013] [Monofunctional monomer] A "monofunctional monomer" is, for example, a monomer having only one polymerizable group in the molecule. Examples of the polymerizable group include polymerizable groups having an ethylenically unsaturated group such as a vinyl group, an acryloyl group, a methacryloyl group, or a styrenyl group. The reversible gas absorption ability of the produced polymer is expressed, for example, by a reaction between an amino group and a gas component or a reaction between an amino group, a gas component, and water. The monofunctional monomer used here may be, for example, one having an amino group or one not having an amino group. Furthermore, a monofunctional monomer having no amino group and a monofunctional monomer having an amino group may be used in combination. When a monofunctional monomer having an amino group is used, the "amine impregnation step" described below does not need to be carried out. Examples of monofunctional monomers not having an amino group include acrylamide, methacrylamide, acrylic acid, acrylic acid salts, methacrylic acid, methacrylic acid salts, 2-acrylamido-2-methylpropanesulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid salts, N-alkylacrylamides, N-alkylmethacrylamides, alkyl acrylates, alkyl methacrylates, N,N-dialkylacrylamides, N-(hydroxyalkyl)acrylamides, (hydroxyalkyl)acrylates, N,N-dialkylmethacrylamides, N-(hydroxyalkyl)methacrylamides, (hydroxyalkyl)methacrylates, and the like. Other substituted (meth)acrylamides can also be used. Specific examples of monofunctional monomers not having an amino group include N-methylacrylamide, N-ethylacrylamide, N-propylacrylamide, N-methylmethacrylamide, N-ethylmethacrylamide, N-propylmethacrylamide, methyl acrylate, ethyl acrylate, propyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, N,N-dimethylacrylamide, N,N-diethylacrylamide, N,N-dipropylacrylamide, N,N-dimethylmethacrylamide, N,N-diethylmethacrylamide, and N,N-dipropylmethacrylamide. Here, the terminal propyl group may be an n-propyl group or an isopropyl group. These monomers not having an amino group may be used alone or in combination of two or more. When the monofunctional monomer has an amino group, the amino group may be a primary amino group, a secondary amino group, or a tertiary amino group. The term "amino group" does not necessarily mean an amino group that constitutes an amide structure (-CO-NR2: R is a hydrogen atom or a substituent). The amino group of the monofunctional monomer may be designed so that its acid dissociation constant (pKa) as a conjugate acid is also designed. In order to increase the carbon dioxide absorption efficiency of the produced polymer, the acid dissociation constant (pKa) of the amino group in the carbon dioxide absorbing environment can be made equal to or greater than the acid dissociation constant (pKa) of carbonic acid. Primary amino groups and some secondary amino groups form strong covalent bonds with carbon dioxide, and may not be able to release the carbon dioxide once it has been absorbed. Therefore, when the monofunctional monomer has an amino group, the amino group may be a secondary amino group or a tertiary amino group, or may be a secondary amino group or a tertiary amino group having a hydroxyl group, an amide group, or an alkyl group in the vicinity, or may be a dialkylamino group such as a dimethylamino group. Furthermore, the amine may be a monofunctional monomer having a cyclic amine such as piperidine or piperazine or a derivative thereof. If the acid dissociation constant of the amino group is too high, carbon dioxide may not be efficiently released during release. Therefore, it is possible to create a crowded environment around the amino groups in the gel by copolymerizing a monomer having a hydrophobic side chain with a monomer having an amino group or by introducing a certain amount of a polyfunctional monomer. The amino group in the monofunctional monomer may be bonded to a portion constituting the main chain of the polymer, or may be bonded to a portion constituting a side chain, but may also be bonded to a portion constituting a side chain. Furthermore, the number of amino groups that the monofunctional monomer has is not particularly limited, and may be one, or two or more. When a monomer has two or more amino groups, each amino group may be the same or different.

[0014] Examples of monomers having an amino group include N-(aminoalkyl)acrylamides, N-(aminoalkyl)methacrylamides, aminoalkyl acrylates, and aminoalkyl methacrylates. In these monomers, the amino group may be substituted with a substituent such as an alkyl group. Specific examples of monomers having an amino group include N,N-dimethylaminopropyl methacrylamide, N,N-diethylaminopropyl methacrylamide, N,N-dimethylaminoethyl methacrylamide, N,N-diethylaminoethyl methacrylamide, N,N-dimethylaminopropyl methacrylate, N,N-diethylaminopropyl methacrylate, N,N-dimethylaminoethyl methacrylate, N,N-diethylaminoethyl methacrylate, N,N-dimethylaminopropyl acrylamide, N,N-diethylaminopropyl acrylamide, N,N-dimethylaminoethyl acrylamide, N,N-diethylaminoethyl acrylamide, 3-aminopropyl methacrylamide, 3-aminopropyl acrylamide, N,N-dimethylaminopropyl acrylate, N,N-diethylaminopropyl acrylate, N,N-dimethylaminoethyl acrylate, N,N-diethylaminoethyl acrylate, 3-aminopropyl methacrylate, and 3-aminopropyl acrylate. Alternatively, the compound may be a salt of an acidic substance, such as a hydrochloride or bicarbonate, or an acrylamide synthesized by condensing a commercially available oligoamine or polyamine having a primary or secondary amine with acrylic acid, methacrylic acid, or a derivative thereof. Furthermore, ethyleneimine, vinylamine, allylamine, allylamine hydrochloride, etc. can also be used as the monomer having an amino group. These monofunctional monomers having an amino group may be used alone or in combination of two or more.

[0015] [Multifunctional monomer] A "polyfunctional monomer" is, for example, a monomer having two or more polymerizable groups in the molecule. For specific examples of the polymerizable group, the description in the [monofunctional monomer] column can be referred to. The number of polymerizable groups possessed by the polyfunctional monomer is not particularly limited, but can be 2 to 6, or 2 to 5, or 2 to 4, or 2. The multiple polymerizable groups possessed by the polyfunctional monomer may be the same or different. By containing the polyfunctional monomer in a predetermined ratio in the reaction mixture, a crosslinked structure is formed between the polymer chains, and a hard polymer with reduced water absorption and swelling can be obtained. By copolymerizing an appropriate amount of a polyfunctional monomer with a monomer having an amino group, hydrophobicity and steric hindrance are introduced around the amino group, and the acid dissociation constant of the amino group under carbon dioxide emission conditions is reduced, allowing the synthesis of a material that efficiently emits carbon dioxide. In this case, if the amount of polyfunctional monomer introduced is too large, the acid dissociation constant of the amino group under carbon dioxide absorption conditions becomes too low, resulting in a decrease in the amount of carbon dioxide absorbed. Therefore, it is important to design the amount of polyfunctional monomer introduced appropriately. Examples of the polyfunctional monomer include polyfunctional (meth)acrylamide monomers, polyfunctional (meth)acrylate monomers, and crosslinkers such as titanium crosslinkers, and an acrylamide monomer (acrylamide derivative) having two polymerizable groups can be used. An example of an acrylamide monomer having two polymerizable groups is N,N'-alkylenebis(meth)acrylamide. Here, the number of carbon atoms in the alkylene group of N,N'-alkylenebis(meth)acrylamide is not particularly limited, but can be 1 to 12, 1 to 4, or 1 to 2. A specific example of an acrylamide derivative having two polymerizable groups is N,N'-methylenebisacrylamide (BIS). Also, instead of the alkylene group, a crosslinking agent having a linear or cyclic crosslinking chain having an amino group, such as oligoethyleneimine, N,N'-bis(2-aminoethyl)-1,3-propanediamine, iminobispropylamine, methyliminobispropylamine, or 1,4-(bisaminopropyl)piperazine, can be used as a polyfunctional monomer. Similarly, instead of the alkylene group, a crosslinking agent in which oligoethylene glycol constitutes a crosslinking chain can be used as a polyfunctional monomer. Also, a specific example of a polyfunctional (meth)acrylate monomer is ethylene glycol dimethacrylate (EGDMA). These polyfunctional monomers may be used alone or in combination of two or more.

[0016] [Monomers with hydrophobic groups] The reaction mixture may include a monomer having a hydrophobic group. "Hydrophobic group" can mean a functional group that is poorly soluble in water, such as an alkyl group or a phenyl group. The monomer having a hydrophobic group may be, for example, a monofunctional monomer having a hydrophobic group and no amino group, or may be a polyfunctional monomer having a hydrophobic group. A monofunctional monomer having both a hydrophobic group and an amino group can be classified as a "monofunctional monomer having an amino group," and a polyfunctional monomer having a hydrophobic group can be classified as a "polyfunctional monomer." Therefore, a monofunctional monomer having a hydrophobic group but not an amino group is called a "monofunctional monomer having a hydrophobic group." The hydrophobic group of the monomer may be, for example, X H 2X Or C X H 2X+1 (X is an integer), and may be a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a tert-butyl group, a pentyl group, a cyclopentyl group, an isopentyl group, a hexyl group, a cyclohexyl group, etc. The hydrophobic group may be one in which a hydrogen atom of the above hydrophobic group is substituted with a hydroxyl group, such as a hydroxyethyl group, a hydroxypropyl group, or a hydroxybutyl group. The hydrophobic group in the monomer may be bonded to the part constituting the main chain of the polymer, or may be bonded to the part constituting the side chain, but may be bonded to the part constituting the side chain. The number of hydrophobic groups that the monomer has is not particularly limited, and may be one, or may be two or more. When the monomer has two or more hydrophobic groups, each hydrophobic group may be the same or different.

[0017] Specific examples of monomers having a hydrophobic group include N-alkylacrylamides, N-alkylmethacrylamides, alkyl acrylates, alkyl methacrylates, N,N-dialkylacrylamides, N-(hydroxyalkyl)acrylamides, (hydroxyalkyl)acrylates, N,N-dialkylmethacrylamides, N-(hydroxyalkyl)methacrylamides, (hydroxyalkyl)methacrylates, N-phenylmethacrylamide, and N-phenyl methacrylate. These polymers having a hydrophobic group may be used alone or in combination of two or more.

[0018] [Combination of monomers] Examples of combinations of monofunctional monomers and polyfunctional monomers include a combination of a monofunctional monomer having an amino group and a polyfunctional monomer, a combination of a monofunctional monomer having neither an amino group nor a hydrophobic group and a polyfunctional monomer, a combination of a monofunctional monomer having a hydrophobic group and a polyfunctional monomer, a combination of a monofunctional monomer having an amino group, a monofunctional monomer having a hydrophobic group and a polyfunctional monomer, and a combination of a monofunctional monomer having an amino group, a monofunctional monomer having neither an amino group nor a hydrophobic group and a polyfunctional monomer. As a combination of a monofunctional monomer having an amino group and a polyfunctional monomer, there can be mentioned a combination of N-(aminoalkyl)(meth)acrylamide and an acrylamide derivative having two polymerizable groups or a (meth)acrylate having two polymerizable groups. A specific example is a combination of N,N-dimethylaminopropyl(meth)acrylamide (DMAPM) and N,N'-methylenebisacrylamide (BIS). As a combination of a monofunctional monomer having an amino group, a monofunctional monomer having a hydrophobic group, and a polyfunctional monomer, there can be mentioned a combination of N-(aminoalkyl)(meth)acrylamide, N-alkyl(meth)acrylamide, and an acrylamide derivative having two polymerizable groups or a (meth)acrylate having two polymerizable groups. A specific example is a combination of N,N-dimethylaminopropyl(meth)acrylamide (DMAPM), N-tert-butylacrylamide (TBAm), and N,N'-methylenebisacrylamide (BIS). Examples of combinations of monofunctional monomers and polyfunctional monomers that do not have amino groups or hydrophobic groups include a combination of N,N-dialkyl(meth)acrylamide and an acrylamide derivative having two polymerizable groups or a (meth)acrylate having two polymerizable groups, and a combination of N-alkyl(meth)acrylamide and an acrylamide derivative having two polymerizable groups or a (meth)acrylate having two polymerizable groups. Specific examples include a combination of N,N-dimethyl(meth)acrylamide (DMAm) and N,N'-methylenebisacrylamide (BIS), and a combination of N-isopropylacrylamide (NiPAm) and N,N'-methylenebisacrylamide (BIS).

[0019] [solvent] The solvent functions as a reaction medium for the polymerization reaction. By including a solvent in the reaction mixture, a polymer can be synthesized with an appropriate amount of space around the amino groups in the polymer. Therefore, the reversible gas absorption capacity of the polymer obtained by adding an appropriate amount of solvent for polymerization tends to be high. Examples of the solvent include polar solvents such as water, alcohol (methanol, ethanol, isopropanol, etc.), and dimethyl sulfoxide, and may be a mixed solvent of two or more of these polar solvents. Also, water or a mixed solvent of water and another polar solvent may be used, and a mixed solvent of water and alcohol, water and ethanol, or water and methanol may be used. The volume ratio of water to alcohol (water:alcohol) may be 1:0 to 1:1, 1:0.2 to 1:0.8, or 1:0.3 to 1:0.5. The solvent may contain salts or polymers soluble in the solvent.

[0020] [Initiator] The initiator is a compound added to start the polymerization reaction of the monomer, and a compound that can be converted into a highly reactive intermediate by the application of energy can be used. For example, a thermal polymerization initiator that generates active species such as radicals and cations by heating, and a photopolymerization initiator that generates active species such as radicals, cations, and anions by light irradiation can be mentioned. Examples of initiators for thermal radical polymerization include azo compounds such as 2,2'-azobis(2-methylpropionitrile) (AIBN), 2,2'-azobisbutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile) (V-65), and 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) (V-70), and peroxides such as benzoyl peroxide, tert-butyl hydroperoxide, hydrogen peroxide, persulfates, and tert-butyl hydroperoxide + ferrous sulfate. Examples of thermal cationic polymerization initiators include benzenesulfonate esters and alkylsulfonium salts. Examples of initiators that generate radicals upon irradiation with ultraviolet light or electron beams include benzoin derivatives, benzyl derivatives, acetophenone derivatives, benzophenone derivatives, and azo derivatives. The initiator such as AIBN may be used after purification (recrystallization) or without purification.

[0021] [Surfactants] If necessary, a surfactant or the like may be added to the reaction mixture, which allows the synthesis of a uniform polymer. As the additive, an amphiphilic polymer such as polyethylene oxide, polyvinylpyrrolidone, polyvinyl alcohol, or an oligomer thereof, or an ionic surfactant such as cetyltrimethylammonium bromide, or the like can be used.

[0022] [Polymerization reaction] In the production method, a polymer is produced by polymerizing monomers in a reaction mixture containing the above-mentioned monofunctional monomer, polyfunctional monomer, solvent, and initiator, and at this time, the total monomer concentration of the reaction mixture can be 0.7 mol / L or more, and the ratio of polyfunctional monomers among the monomers contained in the reaction mixture can be more than 10 mol% and 30 mol% or less. Here, the "total monomer concentration" of the reaction mixture can refer to, for example, the total number of moles of all monomers contained in 1 L of the reaction mixture. When the monomer is polymerized in the above reaction mixture, a polymer having a polymer chain containing a constitutional unit derived from a monofunctional monomer and a crosslinked structure derived from a polyfunctional monomer is synthesized. In this case, in the production method, the total monomer concentration of the reaction mixture can be set to a high value of 0.7 mol / L or more, and in a limited volume of the reaction mixture, the polymer chains can efficiently form non-covalent crosslinking points by interaction and entanglement with each other, and further, the crosslinking agent can be used to polymerize in a state in which the structure is stabilized by covalent crosslinking. As a result, the polymer does not absorb water excessively and does not deform in a wet state. A polymer with low swelling, i.e., a large amount of reversible gas absorption per unit volume, can be synthesized in high yield while maintaining the amount of reversible gas absorption per mass. In addition, the total monomer concentration can be set to 0.7 mol / L or more, and the ratio of polyfunctional monomers among the monomers can be set to 10 mol% or more, so that a relatively dense crosslinked structure can be formed between polymer chains. This allows a polymer to be obtained that is hard and has a lower water content and swelling property. Furthermore, the upper limit of the total monomer concentration can be set to 4 mol / L, and the upper limit of the ratio of polyfunctional monomers can be set to 30 mol%, so that a decrease in the reversible gas absorption amount per mass due to these concentrations being too high can be suppressed. As a result, a polymer material with a large reversible gas absorption amount per unit volume can be produced with good productivity.

[0023] The total concentration of the monomers in the reaction mixture can be, for example, 1.0 to 2.8 mol / L, or 1.5 to 3 mol / L. The proportion of the polyfunctional monomer among the monomers can be, for example, more than 10 mol % and 30 mol % or less, or 15 mol % or more and 30 mol % or less. When the reaction mixture contains a monofunctional monomer having an amino group, the ratio of the monofunctional monomer having an amino group to the monomers can be, for example, 1 to 95 mol %, or 5 to 90 mol %, or 30 to 85 mol %. When the reaction mixture contains a monofunctional monomer having a hydrophobic group, the ratio of the monofunctional monomer having a hydrophobic group to the monomers can be, for example, 1 to 50 mol %, or 5 to 45 mol %, or 10 to 43 mol %. When the reaction mixture contains a monofunctional monomer having an amino group and a monofunctional monomer having a hydrophobic group, the molar ratio of the monofunctional monomer having an amino group to the monofunctional monomer having a hydrophobic group can be, for example, 95:5 to 5:95, or 3:1 to 1:2.

[0024] The procedure for mixing the components of the reaction mixture is not particularly limited, but when a monofunctional monomer having an amino group and a monofunctional monomer having a hydrophobic group are used in combination, the mixture containing the monofunctional monomer having an amino group, the polyfunctional monomer, and water can be heated, and then the monofunctional monomer having a hydrophobic group can be added to the mixture, or the monofunctional monomer having a hydrophobic group can be added to the mixture as an alcohol solution. This allows the monomers to be mixed uniformly while keeping the amount of solvent small. The reaction temperature of the reaction mixture can be, for example, 0 to 200°C, or 30 to 120°C, or 50 to 105°C. The reaction time can be, for example, 0.1 to 5 hours, or 0.2 to 3 hours.

[0025] [Polymer post-treatment] In the production method of the present invention, a low-swelling polymer is formed as a precipitate in the reaction liquid, or the entire reaction liquid is gelled. The formed polymer may be mechanically pulverized to form a slurry or powder, or the liquid components may be removed from the reaction liquid, and the remaining precipitate (polymer) may be mechanically pulverized to form a powder. The obtained powder may also be suspended in a dispersion medium to prepare a slurry. The gel can be crushed using various crushers, such as a jaw crusher, a gyratory crusher, an impact crusher, a roll crusher, an edge runner, a disintegrator, a SAG mill, an autogenous grinding mill, a ball mill, a rod mill, a jet mill, an attritor, an extrusion-shear type crusher, a meat chopper, or a Fitz mill. In addition, the prepared slurry may be applied and dried to form a porous membrane made of polymer powder, or the slurry may be filtered to leave a polymer film on the filter, which may then be dried to form a polymer film or packed layer. In the case of polymer particles used in conventional gas absorbing materials, when the particles absorb moisture and swell, the particles swell and the gaps between the particles are blocked. Therefore, it is difficult to remove the moisture between the particles, and filtration and drying are difficult. In contrast, the powder of the polymer of the present invention has low swelling property, so it can be easily molded into the shape of a membrane or the shape of a packed layer even by a method such as filtration. The polymer molded or filled into a membrane can be stored and then redispersed in water to form a membrane or refill, or can be kneaded with a resin and molded. Examples of the method for applying the slurry include a sand paper method, a spray coating method, a casting method, a bar coating method, a roll coating method, a wire bar coating method, and a dip coating method. The polymer precipitate formed in the reaction solution, and the powder, slurry and film prepared from the precipitate may be freeze-dried or spray-dried. Alternatively, they may be dried with hot air using a fluidized bed. The polymer of the present invention retains a suitable degree of swelling without excessive water absorption even when dispersed in water again after freeze-drying. When reswelling after drying once, an acid such as hydrochloric acid or carbon dioxide may be added. Alternatively, a resin with low volatility and high hydrophilicity such as polyethylene glycol or glycerin may be added during drying in order to accelerate reswelling. Furthermore, the powder, slurry, and membrane prepared from the polymer precipitate, and the freeze-dried products thereof, can be washed as necessary and used as the gas absorbing material described below.

[0026] [2] Amine impregnation process In the manufacturing method of the present invention, the polymer obtained in the polymer synthesis step [1] is impregnated with a treatment liquid containing an amine (hereinafter referred to as "amine-containing treatment liquid") to obtain a polymer material. However, if a monofunctional monomer containing an amino group is used in the polymer synthesis step [1], the amine impregnation step may not be performed. When the polymer is impregnated with the amine-containing treatment liquid, the amine-containing treatment liquid penetrates and diffuses between the polymer chains, and the polymer becomes amine-containing. At this time, the polymer obtained in the above polymer synthesis process is difficult to swell even when impregnated with the amine-containing treatment liquid due to the relatively dense crosslinking structure formed between the polymer chains, and maintains a hard state. The polymer material thus obtained exhibits excellent gas reversible absorption ability, since the swelling of the polymer is suppressed, so that gas is well diffused when filled, and the amino group of the amine or the amino group derived from the monofunctional monomer effectively functions as a functional group that reversibly absorbs gas. The amine-containing treatment solution used in the amine impregnation step and the conditions for the amine impregnation treatment will be described below.

[0027] [Amine-containing treatment solution] The amine-containing treatment liquid used in the amine impregnation step may be any liquid material containing an amine, for example, an amine solution prepared by dissolving an amine in a solvent, or a liquid amine. The amine-containing treatment liquid may also contain a suitable amount of water.

[0028] (Amine) The amine contained in the amine-containing treatment liquid may be either a low molecular weight amine or a high molecular weight amine. The molecular weight of the amine can be, for example, 61-10,000, or 75-1,000, or 90-500. For an explanation and specific examples of compounds that can be used as amines, please refer to the explanation and specific examples of low molecular weight amines in the explanation of absorption enhancers and diffusion enhancers described below.

[0029] (solvent) When an amine solution is used as the amine-containing treatment liquid, the solvent can be, for example, a solvent that can dissolve the amine as a solute, has high compatibility with the polymer, and has high solubility for carbon dioxide and bicarbonate ions. Specific examples include water, ethylene glycol, and glycerin, and may be a mixed solvent of two or more of these solvents. The amine concentration in the amine solution can be, for example, 0.1 to 12 N, or 1 to 10 N, or 3 to 9 N, calculated as the amine concentration.

[0030] (Other Ingredients) The amine-containing treatment liquid may contain components other than the amine and the solvent (other components), such as an antioxidant.

[0031] [Conditions for amine impregnation treatment] Impregnation of a polymer with an amine-containing treatment liquid (amine impregnation treatment) can be carried out, for example, by immersing the polymer in the amine-containing treatment liquid. The polymer to be treated may be dried or swollen with a liquid such as water. When the polymer swollen with a liquid is immersed in an amine-containing treatment liquid, at least a portion of the liquid is replaced with the amine-containing treatment liquid, resulting in a polymer material containing the amine-containing treatment liquid or a mixture of the liquid and the amine-containing treatment liquid therein. The amount of the amine-containing treatment liquid used in the amine impregnation treatment can be, for example, 0.1 to 10 times, or 0.2 to 5 times, or 0.3 to 3 times the mass of the polymer to be treated. The temperature of the amine-containing treatment liquid can be, for example, from 5 to 100°C, or from 10 to 80°C, or from 15 to 60°C. The treatment time for the amine impregnation treatment varies depending on the concentration and temperature of the amine-containing treatment liquid, but can be, for example, 0.1 to 100 hours, or 1 to 24 hours, or 2 to 12 hours. The amine impregnation treatment can be carried out while shaking the amine-containing treatment solution in which the polymer is immersed.

[0032] <Polymer materials> Next, the polymer material of the present invention will be described. The polymer material of the present invention is characterized in that it is produced by the production method of the present invention. For an explanation of the production method of the present invention, the description in the above section <Production method of polymer material> can be referred to. The polymer material of the present invention may be, for example, (A) a polymer having a polymer chain containing a structural unit derived from a monofunctional monomer, a crosslinked structure derived from a polyfunctional monomer, and an amine derived from an amine-containing treatment liquid, or (B) a polymer having a polymer chain containing a structural unit derived from a monofunctional monomer having an amino group, and a crosslinked structure derived from a polyfunctional monomer, and does not contain a component derived from an amine-containing treatment liquid. The monofunctional monomer in the embodiment (A) and the polyfunctional monomer in the embodiment (B) may or may not have an amino group. The polymer material of the present invention can selectively absorb acidic gases such as carbon dioxide and hydrogen sulfide by containing an amino group in at least one of the structural unit of the polymer and the impregnated amine. In addition, by heating, a phase transition such as a decrease in pKa and an increase in hydrophobic interaction of the hydrophobic group occurs, and the absorbed acidic gas is dissipated. That is, the polymer material of the present invention has a gas reversible absorption ability that selectively and reversibly absorbs acidic gases. In addition, since the polymer material of the present invention is manufactured by the manufacturing method of the present invention, it has low water absorption and swelling properties. Therefore, when commercialized as a gas absorbent or gas separation material, the volumetric filling rate can be sufficiently large. In addition, when a gas containing moisture is passed through a gas recovery device to which the product is applied, the polymer absorbs water and swells, but only a limited amount of water can be absorbed, and the degree of expansion is limited. Therefore, the gas flow path can be sufficiently secured, and the amount of heat required for the heating process for gas dissipation can be kept low. In addition, even when liquid water is added to the absorbent material, the gaps between the hydrated polymers are maintained, and the water flow path can be sufficiently secured, and the water can be easily discharged by the subsequent gas flow, and gas can be introduced into the gaps. For these reasons, the polymer material of the present invention can be effectively used as a gas absorption material for reversibly absorbing acidic gases such as carbon dioxide, and the gas absorption material can be effectively used as a gas separation material for separating acidic gases from mixed gases. The average molecular weight of the polymer contained in the polymer material of the present invention, the amount of each group when the polymer has an amino group or a hydrophobic group, the physical properties of the polymer, and the amine content when the polymer material contains an amine will be described below.

[0033] [Average molecular weight of polymer, amount of amino group and hydrophobic group] When the polymer has an amino group, the amount of the amino group can be, for example, 1 mmol / g to 23 mmol / g, or 1 mmol / g to 18 mmol / g, or 2 mmol / g to 7 mmol / g, or the ratio of the monomer having an amino group to the total monomers can be, for example, 5 to 100 mol%, or 30 to 100 mol%, or 50 to 90 mol%. When the polymer has a hydrophobic group, the amount of the hydrophobic group can be, for example, 1 mol % to 50 mol %, or 5 mol % to 45 mol %, or 10 mol % to 43 mol %. The degree of crosslinking of the polymer can be, for example, 0 mol % to 50 mol %, or 5 mol % to 40 mol %, or 10 mol % to 30 mol %. When the polymeric material contains an amine, the content may be, for example, from 1 to 30 mmol / g, or from 2 to 20 mmol / g, or from 3 to 10 mmol / g, of the dry weight of the polymer.

[0034] [Polymer swelling degree] The degree of swelling of the polymer contained in the polymer material of the present invention can be evaluated, for example, by the amount of water it contains when immersed in water for a long period of time.

[0035] [Water content of polymer] The polymeric material of the present invention may contain polymers that, when swollen with an excess of water, contain, for example, 4 grams / gram polymer or less, or 3 grams / gram polymer or less, or 2 grams / gram polymer or less. Here, the "water content" of a polymer refers to the value calculated by the following formula, where M1 is the weight of the wet polymer after adding an excess amount of water, leaving the polymer to stand overnight at room temperature, grinding it with a hand blender, and removing the water by filtration using filter paper or a metal mesh, and M0 is the weight of the polymer when dried by freeze-drying or natural drying. Water content = (M1-M0) / M0

[0036] [Reversible gas absorption capacity of polymer materials] The polymer material can have a reversible CO2 absorption capacity per dry polymer weight of, for example, 30 mL / g or more, 45 mL / g or more, or 60 mL / g or more. This allows the polymer material to efficiently absorb and capture carbon dioxide contained in the exhaust gas when used in a gas capture device that captures carbon dioxide from exhaust gas. For the method of measuring the amount of reversible CO2 absorption, see the description in the (CO2 reversible absorption test) section in the Examples.

[0037] [Polymer material aspects] The form of the polymer material of the present invention is not particularly limited, and may be, for example, any of a powder, a slurry, a film, a bulk body, etc. For the method of producing the powder, the slurry, and the film, the description in the column of [Post-treatment of polymer] in the method of producing the polymer material can be referred to.

[0038] <Gas absorbing materials> Next, the gas absorbing material of the present invention will be described. The gas absorbing material of the present invention comprises the polymeric material of the present invention. The gas absorbing material of the present invention contains the polymer material of the present invention, and has a reversible gas absorbing ability of absorbing acidic gases such as carbon dioxide and hydrogen sulfide or water vapor, and then dissipating the acidic gas or water vapor due to changes in temperature or gas partial pressure. For an explanation of the polymer material of the present invention, please refer to the description in the above column of <Polymer material>. The gas absorbing material of the present invention may contain components other than the polymer material of the present invention (other components) in addition to the polymer material of the present invention. Examples of other components that can be used in the gas absorbing material include moisture, pKa regulators, absorption promoters, diffusion promoters, moisture absorbents, antioxidants, thermoplastic resins, and fillers. Moisture can be incorporated into the gas absorbing material by intentionally adding moisture, for example, using water or water vapor. When adding moisture, for example, carbon dioxide gas or bicarbonate ions can also be added.

[0039] [pKa adjuster] The pKa regulator can be added, for example, during polymerization to adjust the pKa of the polymer after polymerization to a desired value. This allows the type of gas absorbed by the polymer, the type of gas or liquid selectively permeating the gas absorbing material, the permeation flux, the selectivity of the gas to be absorbed relative to other gases, and the like to be controlled. As the pKa regulator, for example, one that can protonate or deprotonate the amino group of the polymer can be used, and for example, an acid such as hydrochloric acid or a base such as sodium hydroxide can be used by adjusting the concentration appropriately according to the desired pKa. In addition, the crosslinking rate by the multifunctional monomer can also adjust the local environment such as the polymer density, the distance between amines, and the polarity around the amine in the polymer to control the PKa of the amine, so the above-mentioned multifunctional monomer may also be used as a pKa regulator. In addition, the addition of hydrophobic monomers, alcohols, and hydrophilic polymers during polymerization can also adjust the local environment such as the polymer density, the distance between amines, and the polarity around the amine to control the pKa of the amine, so these may also be used as pKa regulators.

[0040] [Absorption enhancers, diffusion enhancers] The absorption promoter is a compound having a function of promoting the absorption of acidic gases into the polymer of the present invention. The diffusion promoter is a compound having a function of promoting diffusion of acidic gases from the polymer. In the present invention, an absorption diffusion promoter having both the functions of an absorption promoter and a diffusion promoter may be used. These absorption promoters, diffusion promoters, and absorption diffusion promoters may also function as stabilizers that stabilize the gas absorption material. The total content of the absorption promoter, diffusion promoter, and absorption diffusion promoter in the gas absorption material of the present invention can be, for example, 0.05 mL or more, or 0.1 mL or more per 1 g of solid content. The content of the absorption promoter in the gas absorption material can be, for example, 0.1 to 12 N, 1 to 10 N, or 3 to 9 N in terms of amine concentration. A low molecular weight amine can be used as the absorption promoter, diffusion promoter, or absorption diffusion promoter. The molecular weight of the low molecular weight amine may be, for example, 61 to 10,000, or 75 to 1,000, or 90 to 500. The boiling point of the low molecular weight amine can be, for example, 80°C or higher, 120°C or higher, or 150°C or higher, since it can be used for a long time and is practical. An amine-containing compound that has a site that forms a salt with a counter ion like an ionic liquid and becomes liquid to increase the boiling point may be used. The low molecular weight amine may contain any of a primary amino group, a secondary amino group, a tertiary amino group, an ammonium group, and an imidazolium group, and may contain a plurality of amino groups, ammonium groups, and imidazolium groups, for example, 1 to 3 groups. The secondary amino group and the tertiary amino group may be cyclic amino groups. Furthermore, the low molecular weight amine may contain a functional group other than an amino group, an ammonium group, and an imidazolium group, for example, a hydroxyl group. The low molecular weight amine may contain 0 to 2 hydroxyl groups. Examples of the low molecular weight amine include amines having an amino group and a hydroxyl group, and amines having three amino groups, for example, amines having a secondary amino group and a hydroxyl group. Since the amount of acidic gas released can be increased dramatically especially in a high concentration range and is suitable for repeated use, for example, an amine having a secondary amino group and a hydroxyl group with a boiling point of 150°C or more may be selected. Examples of low molecular weight amines include specific compounds represented by the following formula:

[0041] [ka]

[0042] Among these, DMAE, IPAE, Bis(2DMAE)ER, 1-2HE-PRLD, 1-2HE-PP, TM-1,4-DAB, TMHAD, and PMDETA may be selected since they can increase the amount of acidic gas emitted. Among these, IPAE, Bis(2DMAE)ER, 1-2HE-PP, TM-1,4-DAB, TMHAD, and PMDETA may be selected since they have a relatively high boiling point and are difficult to evaporate. IPAE, TM-1,4-DAB, TMHAD, and PMDETA may be selected since increasing their concentration can significantly increase the amount of acidic gas emitted. IPAE, TMHAD, and PMDETA may be selected since they are easily available.

[0043] [Moisture absorbent] The moisture absorbent that can be used as an additive can be, for example, one that has a relative humidity of 90% or less at 25°C when it is made into a saturated aqueous solution. Examples of such moisture absorbents include ions such as bromide ions, chloride ions, acetate ions, carbonate ions, bicarbonate ions, lithium ions, potassium ions, calcium ions, magnesium ions, and sodium ions. Examples of such moisture absorbents include salts such as lithium bromide, lithium chloride, calcium chloride, potassium acetate, magnesium chloride, potassium carbonate, and sodium carbonate. When a moisture absorbent is added, the amount of the moisture absorbent added can be, for example, 0.01 to 10% by mass based on the total amount of the gas absorbing material.

[0044] [Antioxidants] The antioxidant that can be used as an additive is one that can suppress or prevent oxidation by adding it. Examples of such antioxidants include vitamin C (ascorbic acid), vitamin E (tocopherol), BHT (dibutylhydroxytoluene), BHA (butylhydroxyanisole), sodium erythorbate, propyl gallate, sodium sulfite, sulfur dioxide, hydroquinone and its derivatives. When an antioxidant is added, the amount of the antioxidant added can be, for example, 0.01 to 10% by mass based on the total amount of the gas absorbing material.

[0045] [Thermoplastic resin] The gas absorbing material may contain a thermoplastic resin, which can be mixed with the polymer of the present invention and other components, if necessary, and formed into pellets or a film. As the thermoplastic resin, known ones can be used. For example, polyolefins such as polyethylene, polypropylene, and ethylene-vinyl acetate copolymers, modified polyolefins, polyamides, thermoplastic polyimides, and liquid crystal polymers such as aromatic polyesters, polyphenylene oxides, polyphenylene sulfides, polycarbonates, polymethyl methacrylates, polyethers, polyether ether ketones, polyetherimides, polyacetals, styrenes, polyolefins, polyvinyl chlorides, polyurethanes, and polyesters such as polyethyl lactate, polyamides, polybutadienes, trans-polyisoprenes, fluororubbers, and chlorinated polyethylenes such as polyvinyl chloride and polyvinylidene chloride, and various thermoplastic elastomers, or copolymers, blends, and polymer alloys mainly made of these, for example, polyolefin resins such as polyethylene can be selected. When a thermoplastic resin is contained in the gas absorbing material, the content of the thermally activated resin can be, for example, 10 to 40% by mass with respect to the total amount of the gas absorbing material.

[0046] [Filler] The gas absorbing material may contain a filler. This can form voids in the gas absorbing material, promoting the diffusion of gas into the gas absorbing material, and improving the reversible absorption rate and reversible absorption amount of gas. Furthermore, by using a filler having gas adsorption ability, it is possible to achieve gas adsorption of the adsorbent in addition to the gas absorption of the absorbing material. It is known that gas adsorbents exhibit large gas reversible adsorption ability at low humidity, and gas absorbing materials exhibit large gas absorption performance at high humidity, so by using a gas adsorbent as a filler, a material having large gas reversible adsorption ability under a wide range of humidity conditions can be realized. As the filler having gas adsorption ability, for example, materials having a large pore area such as various activated carbons and zeolites may be used. An adsorbent having a particularly large carbon dioxide gas adsorption ability may be selected and used. In addition, when the polymer material constituting the gas absorbing material is gelled by containing water or is a pulverized product of a gelled polymer (polymer pulverized product), adding a filler reduces the bulk and increases the loading amount, thereby improving the reversible gas absorption ability. For the filler, fine particles having a primary particle diameter of 1000 nm or less, which will be described later, can be preferably used. Furthermore, the gas reversible absorption capacity can be further improved by pulverizing the gas absorbing material containing the pulverized polymer and the filler. The pulverization of the gas absorbing material containing the pulverized polymer and the filler can be performed using a planetary ball mill device using a bead mill or the like. In order to promote the diffusion of gas into the inside of the absorbing material, the filler may be selected to be in a powder form. Also, fillers having an average particle size of, for example, 1000 nm or less may be adopted. The primary particle size here can be measured by observation with a transmission electron microscope. The fine particles having a primary particle size of 1000 nm or less used in the present invention may be composed only of fine particles having a primary particle size of 1000 nm or less. The particle size can be 0.1 nm to 1000 nm, or 0.3 nm to 500 nm, or 0.5 nm to 300 nm, or 1 nm to 200 nm, or 1.5 nm to 100 nm, or 2 nm to 50 nm, or 2.5 nm to 25 nm in terms of average primary particle size. This makes it possible to more reliably form a gas diffusion phase in the molded body of the gas absorbing material, and tends to further improve the absorption rate and emission rate of gas. The fine particles may be those in which the primary particles are aggregated. The aggregates are preferably 100 nm to 200 μm, more preferably 500 nm to 100 μm, and most preferably 2.5 μm to 50 μm. Among fillers, those having a water contact angle of, for example, 70° or more may be used. The water contact angle may be 80° or more, or 100° or more, or 110° or more, or 120° or more, or 130° or more, or 140° or more.

[0047] Fine particles with a primary particle size of 1000 nm or less In the following, fine particles having a primary particle size of 1000 nm or less that can be used as a filler will be specifically described. The particles having a primary particle diameter of 1000 nm or less may be made of an inorganic material, an organic material, or a combination of an organic material and an inorganic material. The particles may be water-repellent or hydrophilic, but are preferably water-repellent. By using water-repellent particles, the voids formed by the particles are prevented from being blocked by the moisture contained in the gas absorbing material, and the voids function effectively as a gas diffusion phase. Here, "water-repellent fine particles" refers to fine particles having a primary particle diameter of 1000 nm or less and a water contact angle of 70° or more. The "water contact angle" of fine particles refers to the contact angle with water measured on the surface of a fine particle deposition film formed from the fine particles. The water contact angle of the fine particle deposition film surface can be measured by static contact angle measurement with water. The water contact angle of the water-repellent microparticles is preferably 80° or more, more preferably 100° or more, even more preferably 110° or more, even more preferably 120° or more, particularly preferably 130° or more, and most preferably 140° or more.

[0048] (Water-repellent particles) The water-repellent fine particles having a primary particle diameter of 1000 nm or less may be fine particles that are water-repellent themselves, or may be particles (substrate particles) that have been given water-repellency on their surfaces as base materials. Examples of fine particles having water-repellency on the surfaces of base particles include coated fine particles in which a water-repellent coating is formed on the surface of a base particle, and surface-modified fine particles in which a surface modification is performed on a base particle to give it water-repellency. First, carbon black can be given as an example of fine particles that are water repellent by themselves. Examples of carbon black include acetylene black, furnace black, channel black, thermal black, lamp black, and ketjen black, and among these, acetylene black is preferred. Other examples of water-repellent fine particles include fine particles made of Knobel (porous carbon, manufactured by Toyo Tanso Co., Ltd.), titanium oxide, mesoporous silica, and the like. In addition, fine particles formed of a water-repellent organic material can also be used as fine particles that are water-repellent themselves. 1 A 2 -CA 3 A 4 )-(wherein A 1 ~A 4represents a hydrogen atom, a fluorine atom, a chlorine atom or a perfluoroalkyl group; A 1 ~A 4 At least one of the fluorine atoms is a fluorine atom). Specific examples of fluororesins include polytetrafluoroethylene (PTFE), copolymers of tetrafluoroethylene and other monomers, polychlorotrifluoroethylene (PCTFE), copolymers of chlorotrifluoroethylene and other monomers, polyvinylidene fluoride (PVDF), polyvinyl fluoride (PVF), polytetrafluoropropylene (HEP), and the like. Examples of copolymers of tetrafluoroethylene and other monomers include perfluoroalkoxyalkane (PFA: tetrafluoroethylene and perfluoroalkyl vinyl ether copolymer), perfluoroethylene propene copolymer (FEP: tetrafluoroethylene and hexafluoropropylene copolymer), ethylene-tetrafluoroethylene copolymer (ETFE), tetrafluoroethylene-perfluorodioxole copolymer (TFE / PDD), and the like. Examples of copolymers of chlorotrifluoroethylene and other monomers include ethylene-chlorotrifluoroethylene copolymer (ECTFE). These water-repellent organic materials may be used alone or in combination of two or more.

[0049] The base particles of the coated particles and surface-modified particles may be inorganic or organic particles, but are preferably inorganic particles. In addition, when a base particle made of a water-repellent particle itself is used and the particle is subjected to a surface modification to impart a water-repellent coating or water repellency, the gas absorption rate and emission rate as well as the amount of gas absorption and emission can be improved. As the inorganic particles, known ones can be used, and examples thereof include carbon black such as acetylene black, furnace black, channel black, thermal black, lamp black, and Ketjen black, particles made of inorganic compounds such as oxides, hydroxides, nitrides, halides, carbonates, sulfates, acetates, and phosphates of metal elements or semimetal elements, and natural mineral particles. Examples of inorganic compounds of metal elements or semimetal elements include lithium fluoride, calcium carbonate, calcium phosphate, calcium sulfate, calcium fluoride, barium sulfate, titanium dioxide (titania), zirconia dioxide (zirconia), aluminum oxide (alumina), alumina silicate (alumina silicate, kaolin, kaolinite), silicon oxide (silica, silica gel), and examples of natural minerals include talc and clay. Among these, particles made of carbon black and silicon oxide are preferred. As the organic particles, known ones can be used, and examples of the organic particles include particles made of styrene-based, acrylic-based, melamine-based, benzoguanamine-based, and silicone-based polymers. In this case, a filler may be used in combination, and for example, activated carbon or zeolite can be preferably used as the filler.

[0050] The water-repellent coating formed on the base particle can be made of the water-repellent organic material exemplified above as the water-repellent material usable for forming the microparticles, as well as a coating of organopolysiloxane or organohydrogenpolysiloxane. Examples of organopolysiloxane include dialkylpolysiloxane and alkylphenylpolysiloxane, and examples of organohydrogenpolysiloxane include alkylhydrogenpolysiloxane. The alkyl group in the dialkylpolysiloxane, alkylphenylpolysiloxane, and alkylhydrogenpolysiloxane may be linear, branched, or cyclic, but is preferably linear. The number of carbon atoms in the alkyl group is preferably 1 to 20, more preferably 1 to 10, and even more preferably 1 to 6. Here, the two alkyl groups bonded to the silicon atom may be the same or different from each other. Specific examples of the organopolysiloxane include dimethylpolysiloxane and methylphenylpolysiloxane, and a specific example of the organohydrogenpolysiloxane includes methylhydrogenpolysiloxane.

[0051] The surface modification method for the base particle can include a method of introducing water-repellent groups such as an alkyl group or a fluorinated alkyl group into the surface of the base particle. The alkyl group or fluorinated alkyl group introduced into the base particle may be linear, branched, or cyclic, but is preferably linear. The number of carbon atoms in the alkyl group or fluorinated alkyl group is preferably 1 to 20, more preferably 1 to 15, and even more preferably 1 to 10. The fluorinated alkyl group may be a partially fluorinated alkyl group in which some of the hydrogen atoms of the alkyl group are substituted with fluorine atoms, or a perfluoroalkyl group in which all of the hydrogen atoms are substituted with fluorine atoms.

[0052] The surface modification for introducing these water-repellent groups into the base particles can be carried out using a silane coupling agent or a silane compound such as silazane. Examples of the silane coupling agent include compounds represented by the following general formula (1). General formula (1) R 1 n Six (4-n) In the general formula (1), X represents a hydrolyzable group that generates a silanol group upon hydrolysis, and R 1 represents a group containing a water-repellent group, and n is an integer of 1 to 3. In the silane coupling agent represented by general formula (1), a silanol group or a silyl group produced by hydrolysis of X reacts with a functional group on the surface of the base particle, thereby introducing a water-repellent group into the base particle. In the general formula, examples of the "hydrolyzable group that forms a silanol group" represented by X include alkoxy groups such as methoxy and ethoxy groups, and halogen groups. R 1 Examples of the water-repellent group in the above formula include an alkyl group, a fluorinated alkyl group, and dimethylsiloxane. The description and preferred range of the alkyl group and the fluorinated alkyl group can be referred to the description and preferred range of the water-repellent group that can be introduced to the surface of the base particle. The water-repellent group may be directly bonded to Si or may be bonded via a linking group. n is an integer of 1 to 3, and is preferably 1 or 2. When n is 2 or more, a plurality of R 1 may be the same or different. When n is 2 or less, multiple Xs may be the same or different. Examples of the silane coupling agent represented by the general formula (1) include triethoxyalkylsilane, diethoxydialkylsilane, ethoxytrialkylsilane, trimethoxyalkylsilane, dimethoxydialkylsilane, methoxytrialkylsilane, trichloroalkylsilane, etc. Specific examples of the silane coupling agent include triethoxycaprylylsilane (triethoxy-n-octylsilane), octadecyltrichlorosilane, etc. The formation of the water-repellent coating on the base particles and the surface modification treatment can be carried out according to a conventional method.

[0053] Commercially available water-repellent microparticles include Microdispers-200 (manufactured by Techno Chemical Co., Ltd.), AEROSIL RY200, AEROSIL RY300, AEROSIL R805 (all manufactured by Evonik), and Ketjen Black (manufactured by Lion Specialty Chemicals Co., Ltd.). The water-repellent fine particles may be used alone or in combination of two or more kinds.

[0054] (Fine particles other than water-repellent fine particles) The fine particles having a primary particle diameter of 1000 nm or less that can be used as a filler are not limited to water-repellent fine particles, and may be fine particles other than water-repellent fine particles, i.e., fine particles having a water contact angle of less than 70°. In addition, water-repellent fine particles may be used in combination with fine particles having a water contact angle of less than 70°. The fine particles having a water contact angle of less than 70° may have a water contact angle of 50° or less, 30° or less, or 10° or less. The lower limit of the water contact angle of the fine particles is 0°. Examples of fine particles other than the water-repellent fine particles include particles made of inorganic compounds of metal elements and semimetal elements and organic particles described as examples of base particles of coated fine particles and surface-modified fine particles in the above section (water-repellent fine particles), and it is preferable to use silicon oxide particles. Furthermore, these inorganic particles and organic particles may have a coating of an organic compound formed on their surfaces, or an organic functional group may be introduced therein. An example of a commercially available product of fine particles other than the water-repellent fine particles is AEROSIL 200 (manufactured by Evonik).

[0055] (specific surface area of ​​fine particles) The specific surface area of ​​the fine particles is 1 to 3000 m 2 / g, and 2.5 to 2750m 2 / g is more preferable, and 5 to 2500m 2 This makes it possible to more reliably form a gas diffusion phase in the molded article of the gas absorbing material, and tends to further improve the gas absorption rate and gas emission rate. The specific surface area of ​​the fine particles can be measured by the BET method.

[0056] Ratio of polymer material to fine particles with a primary particle diameter of 1000 nm or less The compounding ratio by weight of the solid content of the polymer material and the fine particles (polymer material: fine particles) is preferably 95:5 to 5:95, more preferably 90:10 to 30:70, and even more preferably 80:20 to 50:50. The content of the polymer material in the gas absorbing material is preferably greater than the content of the water-repellent fine particles in terms of solid content. When the polymer material contains water and is gelled, or is a pulverized product of the gelled polymer, adding a filler to the gas absorbing material reduces the bulk and increases the loading amount, thereby improving the reversible gas absorption performance. From the viewpoint of effectively obtaining such an action, the volume ratio of the gelled polymer or its pulverized product to the fine particles (gelled polymer or its pulverized product: fine particles) is preferably 99.9:0.1 to 98:2, more preferably 99.75:0.25 to 98.5:1.5, and even more preferably 99.5:0.5 to 99:1. By setting the ratio of the polymer material to the fine particles within the above range, the gas absorption rate and the gas emission rate tend to be higher. However, the gas absorbing material of the present invention is not limited to those containing fine particles having a primary particle diameter of 1000 nm or less. In other words, the gas absorbing material of the present invention does not have to contain fine particles having a primary particle diameter of 1000 nm or less.

[0057] Other fillers In addition to the fine particles exemplified above, known fillers can be used in the gas absorbing material of the present invention. For example, activated carbon, zeolite, silica, fumed silica, hydrophobized silica, hydrophobized fumed silica, water-repellent silica, alumina, hydrophobized alumina, water-repellent alumina, boehmite, diatomaceous earth, oxides such as titanium oxide, iron oxide, zinc oxide, magnesium oxide, and metal ferrite, hydroxides such as aluminum hydroxide and magnesium hydroxide, carbonates such as calcium carbonate (light and heavy), magnesium carbonate, dolomite, and dawsonite, sulfates or sulfites such as calcium sulfate, barium sulfate, ammonium sulfate, and calcium sulfite, talc, mica, clay, glass fiber, Examples of the filler include silicates such as calcium silicate, montmorillonite, and bentonite; borates such as zinc borate, barium metaborate, aluminum borate, calcium borate, and sodium borate; carbon such as carbon black, hydrophobized carbon black, water-repellent carbon black, graphite, and carbon fiber; and other carbons such as iron powder, copper powder, aluminum powder, zinc oxide, molybdenum sulfide, boron fiber, potassium titanate, lead zirconate titanate, fluorinated resin powder, and Teflon (registered trademark) powder. Hydrophobic substances can also be selected and used to suppress condensation and dew of water vapor. Carbon such as carbon black can also be selected and used. These fillers may have a primary particle diameter of 1000 nm or less or more than 1000 nm. The gas absorbing material of the present invention may also contain particles made of the same material as those exemplified as fine particles having a primary particle diameter of 1000 nm or less, and have a primary particle diameter of more than 1000 nm. When the gas absorbing material contains a filler, the content of the filler can be, for example, 0.1 to 60 mass % based on the total amount of the gas absorbing material.

[0058] [Dispersion medium] The gas absorbing material may contain a dispersion medium for suspending the polymer material of the present invention and the additive. For the preferred range and specific examples of the dispersion medium, please refer to the description in the [Solvent] section of the method for producing the polymer material.

[0059] The other components that can be used in the gas absorbing material described above may be used alone or in combination of two or more.

[0060] <Use of gas absorbing material> The gas absorbing material containing the polymer material of the present invention can be used in various ways. Examples of the usage of the gas absorbing material include filling a container such as a drum with the gas absorbing material, forming the gas absorbing material into a sheet and forming a laminate or roll with nonwoven fabric or mesh, filling the gas absorbing material inside a filter, kneading the gas absorbing material with a hard material such as polyethylene and forming it into a self-supporting film, fiber, or pellet, supporting a film of the gas absorbing material with a carrier, filling the gas absorber powder inside a honeycomb structure, etc. When forming the gas absorbing material into a sheet or film, its thickness is not particularly limited, but can be, for example, 1 to 10,000 μm, 10 to 5,000 μm, or 100 to 1,000 μm. When the gas absorbing material is supported by a carrier, the carrier may be a thin plate, a fiber assembly, etc. The thin plate and the fiber assembly that can be used as the carrier will be described below.

[0061] [Thin plate] The thin plate may be a flat plate, sheet, or foil having a thickness of, for example, 2 mm or less and 5 μm or more. The material of the thin plate has a specific heat at constant pressure of, for example, 2500 KJ / (m 3 A thin plate having a thermal conductivity of 10 W / (mK) or less may be used, and a thin plate having a thermal conductivity of 10 W / (mK) or more may be used. A thin plate having such thermal properties changes temperature responsively in response to changes in the external temperature, and can efficiently transmit the temperature change to the entire gas absorbing material. In this specification, the term "constant pressure specific heat" refers to a value measured by a calorimeter such as a water calorimeter or a differential scanning calorimeter, and the term "thermal conductivity" refers to a value measured by a laser flash method or a steady heat flow method.

[0062] As the thin plate, a metal thin plate (metal foil), a sheet made of a carbon material, a carbon sheet, a resin film (polymer compound film), etc. can be used. As the sheet made of a carbon material, a graphite sheet, etc. can be exemplified, and as the resin film, polyethylene, polypropylene, PET, polyimide, etc. can be exemplified. As the thin plate, for example, an aluminum thin plate, an iron thin plate, or a graphite sheet may be used because of its high thermal conductivity. Alternatively, as for example, an aluminum thin plate, a graphite sheet, or a resin film may be used because of its low specific heat. In addition, as the thin metal plate, for example, a stainless steel thin plate, an iron thin plate, an aluminum thin plate, or a nickel thin plate, etc. can be exemplified, and among these, an iron thin plate, an aluminum thin plate, or a nickel thin plate may be particularly selected because of its relatively high thermal conductivity.

[0063] The thin plate may be a plate having a homogeneous internal structure, or may be a porous body or a honeycomb structure. In the case of a porous body or a honeycomb structure, the pores can be filled with a gas absorbing material, so that the heat of the thin plate can be easily transferred to the gas absorbing material, and the responsiveness of the gas absorbing material to temperature changes can be improved. In particular, porous bodies such as foamed metal, foamed nickel, and porous carbon have high heat conductivity to the gas absorbing material, and by using them as a carrier, the responsiveness of the gas absorbing material to temperature changes can be greatly improved. The pore size of the porous body such as foamed metal can be, for example, 0.1 to 10 mm, or 0.4 to 4 mm. The specific surface area can be, for example, 100 to 10,000 m 2 / m 3 , or 200~6000m 2 / m 3 In addition, when a carrier made of a porous resin or porous carbon is used as the porous carrier, the thermal efficiency of the absorber can be improved because the heat capacity is small. The porous body used as the carrier may be selected to have a porosity of, for example, 1 to 99%, 10 to 99%, or 20 to 95%. In this specification, the "porosity of the thin plate" means the porosity measured by the apparent volume and mass of the thin plate and the density of the material. The carrier may also be a laminate of a plurality of these thin plates. In the laminate, all the thin plates may be the same, or a plurality of thin plates of different materials or thicknesses may be combined.

[0064] [Fiber assembly] The fiber aggregate is a material obtained by processing a large number of fibers into a thin, wide plate shape. Examples of the fiber aggregate include cloth and paper, and among them, it is preferable to use a porous one such as a filter. The cloth may be any of woven cloth, felt, and nonwoven cloth. Sintered metal fiber felt can also be used as the carrier. This has a shape in which fibers, which are sintered fiber bodies, are densely assembled, and can obtain high heat conductivity. For example, sintered felt made of stainless steel fibers or sintered felt made of nickel fibers can be used, and among them, sintered felt made of nickel fibers can be selected and used. The fibers used in the fiber assembly have a specific heat at constant pressure of, for example, 2500 KJ / (m 3 It is also possible to use a fiber assembly having a thermal conductivity of 10 W / (mK) or less and a thermal conductivity of 10 W / (mK) or more. A fiber assembly having such thermal properties changes temperature responsively in response to changes in the external temperature, and can efficiently transmit the temperature change to the entire gel membrane.

[0065] The fibers used in the fiber assembly may be inorganic fibers, organic fibers, or composite fibers that combine inorganic and organic fibers. Examples of inorganic fibers include stainless steel fibers, aluminum fibers, metal fibers such as nickel fibers, and carbon fibers. Nickel fibers may be selected because of their high thermal conductivity. As organic fibers, any of natural fibers such as cotton and hemp, and synthetic fibers such as rayon and polyester can be used. The diameter of the fibers is not particularly limited, but for example, fibers having a diameter of 8 to 100 μm can be used, which makes it possible to obtain a membrane of the gas absorbing material having excellent gas absorption and diffusion properties. The carrier may be an assembly in which a plurality of these fiber assemblies are laminated. In the assembly, each fiber assembly may be the same, or a plurality of fiber assemblies having different fiber types, fiber diameters, fiber densities, etc. may be combined. The carrier may be a laminate in which a thin plate and a fiber assembly are laminated.

[0066] The shape of the carrier is not particularly limited and can be appropriately selected depending on the application. Specific examples of the shape of the carrier include a plate shape and a cylinder shape, and the planar shape of the plate and the cross-sectional shape of the cylinder may be any of a polygonal shape such as a square shape or a rectangle shape, a perfect circle shape, an ellipse shape, and the like. The gas absorbing material supported on the carrier can be formed by applying a slurry or powder of the gas absorbing material to the surface of the carrier, or by laminating a film of the gas absorbing material that has been previously formed on the surface of the carrier. A binder may be used to stably fix the slurry or powder of the gas absorbing material to the carrier.

[0067] <Gas recovery equipment> As described above, the gas absorbing material of the present invention can reversibly absorb acidic gases such as carbon dioxide and water vapor, and since the swelling property of the polymer component is low, the volume filling rate can be increased when commercialized as a gas absorbent or the like. Therefore, it can be suitably used as a material for a gas absorber of a gas recovery device that selectively recovers carbon dioxide from exhaust gas, for example. Hereinafter, a first embodiment and a second embodiment of a gas recovery device to which the gas absorbing material of the present invention is applied will be described. FIG. 1 is a schematic diagram showing a gas recovery device of the first embodiment, and FIG. 2 is a schematic diagram showing a gas recovery device of the second embodiment.

[0068] As shown in FIG. 1, the gas recovery device of the first embodiment includes a heat exchanger 21, a desulfurizer 22, a cylindrical gas absorber 23, and first to third pipes 24, 25, and 26 connected to each of these parts. One end of the first pipe 24 is a gas inlet for introducing exhaust gas (gas to be treated), and the other end is connected to the desulfurizer 22. One end of the second pipe 25 is connected to the desulfurizer 22, and the other end is connected to one side of the gas absorber 23. The third pipe 26 has a circulation path 26a connected to, for example, one side and the other side of the gas absorber 23, and a branch path 26b branching from the circulation path 26a on the one side of the gas absorber 23, and one end of the branch path 26b is a gas outlet for discharging the recovered carbon dioxide gas. The connecting portions of the second pipe 25 and the third pipe 26 on one side surface of the gas absorber 23 are provided, for example, on substantially the same diameter of the circular side surface, so as to sandwich the center. The heat exchanger 21 is connected to the middle part of the first pipe 24 and the middle part of the circulation path 26a. The gas absorber 23 is made of the gas absorbing material of the present invention, and when the gas recovery device is turned off, its temperature is approximately the same as the ambient temperature. The gas absorber 23 may be formed in a filter shape and disposed at a position where at least a part of it passes through the gas flow path in the gas recovery device. Moreover, the gas absorber 23 may not be in the form of a filter, but may be disposed at a position at least partially removed from the gas flow path in the gas recovery device.

[0069] To recover carbon dioxide from exhaust gas using this gas recovery device, the operation of each part is turned on, and the high-temperature exhaust gas with dust collection is introduced from one end of the first pipe 24. The introduced exhaust gas passes through the first pipe 24 and is introduced into the desulfurizer 22 having a cooling capacity of about 30°C. Here, the desulfurizer and the cooler may be separate devices. In addition, the temperature of the gas after passing through the desulfurizer 22 having a cooling capacity does not need to be 30°C, and may be about 40°C or 50°C. When passing through the first pipe 24, a part of the heat of the exhaust gas is transferred to the circulation path 26a of the third pipe 26 via the heat exchanger 21, and the temperature is adjusted so that the gas temperature or the dew point temperature of the gas in the circulation path 26a is heated to about 60°C. The heating of the gas in the circulation path 26a may be heating with heated water. The temperature or dew point temperature of the gas in the circulation path 26a may be 60°C or higher, and may be about 75°C or 85°C. In addition, the gas in the circulation path 26a may be depressurized. When the gas in the circulation path 26a is decompressed and the gas in the circulation path 26a is heated by heated water, there may be no gas flow in the circulation path 26a or the gas flow rate may be very low. The exhaust gas introduced into the desulfurizer 22 flows into the second pipe 25 after being desulfurized in the desulfurizer 22. The exhaust gas that flows into the second pipe 25 has a temperature or dew point temperature of about 30°C, and is introduced into the gas absorber 23 at about this temperature. In the gas absorber 23, since the temperature of the exhaust gas is about 30°C, the absorber is cooled in the region where the exhaust gas comes into contact, and acid gases such as carbon dioxide are efficiently absorbed by the gas absorption material, and gases other than carbon dioxide are discharged to the outside of the gas absorber 23. When the dew point temperature of the exhaust gas is lower than the temperature of the absorption material, the absorption material and the exhaust gas are effectively cooled by the evaporation of water from the absorption material, and the temperature can be suitably controlled. In addition, if the cooling of the absorber by the cooled exhaust gas is insufficient, additional cooling can be performed, such as cooling using the latent heat of evaporation of water by introducing a cooling gas or reducing pressure or introducing a dry gas. Meanwhile, the region of the gas absorber 23 that has absorbed carbon dioxide moves to the vicinity of the connection part of the third pipe 26 due to the rotation of the gas absorber 23, and comes into contact with the gas introduced from the circulation path 26a of the third pipe 26.Since the gas introduced from the circulation path 26a is heated to about 75°C by heat exchange with the exhaust gas, the gas absorbing material is heated in the gas absorber 23 in the region where the gas comes into contact, and acidic gases such as carbon dioxide are released. At this time, if the dew point temperature of the gas in the circulation path 26a is higher than the temperature of the absorbing material, the absorbing material is more effectively heated by the heat of condensation of the water vapor, which is preferable. Also, even if the gas in the circulation path 26a is decompressed, it becomes possible to release carbon dioxide effectively due to the reduction in the partial pressure of carbon dioxide. A part of the released carbon dioxide flows into the branch path 26b of the third pipe 26, and is discharged to the outside from the gas outlet of the branch path 26b and recovered. The other part of the released carbon dioxide flows into the circulation path 26a of the third pipe 26. The carbon dioxide that flows into the circulation path 26a is heated or humidified by the heat exchanger 21 in the middle of the circulation path 26a, and then reintroduced into the gas absorber 23, and the heat is used to heat the gas absorbing material.

[0070] As described above, in the carbon dioxide gas recovery device of the first embodiment, the heat of the exhaust gas is reused to heat the gas absorber, and switching is performed from a state in which acid gas is absorbed to a state in which it is dissipated. In this embodiment, the heat of the exhaust gas is effectively utilized, so that the amount of energy consumed in the carbon dioxide gas separation and recovery process can be significantly reduced. In the first embodiment, if the temperatures of the exhaust gas and the gas absorber cannot be controlled to a temperature suitable for the absorption and dissipation of carbon dioxide, the temperature control is improved by adding an external heat exchange mechanism or an additional heating mechanism to the piping and the absorber.

[0071] Next, a second embodiment of the gas recovery device will be described. As shown in FIG. 2, the gas recovery device of the second embodiment has a first heat exchanger 31, a second heat exchanger 32, a desulfurizer 33, a first tank 34, a second tank 35, and a first pipe 36 and a second pipe 37 connected to each of these parts. One end of the first pipe 36 is a gas inlet for introducing exhaust gas (gas to be treated), and the other end is connected to the desulfurizer 33 having a cooling capacity. Here, the desulfurizer and the cooler may be separate devices. The second pipe 37 has a main path 37a, one end of which is connected to the desulfurizer 33, and a first path 37b and a second path 37c branched at the other end of the main path 37a. One end of the first path 37b is connected to the main path 37a, and the other end is connected to the first tank 34. One end of the second path 37c is connected to the main path 37a, and the other end is connected to the second tank 35. Valves (not shown) for opening and closing each of the first and second paths 37b, 37c are provided near the other ends of the first and second paths 37b, 37c. The first heat exchanger 31 is connected to a first intermediate portion of the first pipe 36 and the first tank 34, and the second heat exchanger 32 is connected to a second intermediate portion of the first pipe 36 and the second tank 35, respectively. In the gas recovery device of the second embodiment, gas absorbing materials (gas absorbers) 38, 39 are formed on the heat exchange surface of the first heat exchanger 31 in the first tank 34 and the heat exchange surface of the second heat exchanger 32 in the second tank 35, respectively, and when the operation of the gas recovery device is OFF, each gas absorber 38, 39 is at a temperature similar to the ambient temperature (approximately 30°C).

[0072] To recover carbon dioxide gas from exhaust gas using this carbon dioxide gas recovery device, first, the valve of the first path 37b of the second pipe 37 is opened, the valve of the second path 37c of the second pipe 37 is closed, the first heat exchanger 31 is turned off, and the second heat exchanger 32 is turned on. In this state, the first tank 34 functions as an absorption tower. That is, in this state, when the high-temperature exhaust gas after dust collection is introduced from one end of the first pipe 36, the introduced exhaust gas passes through the first pipe 36 and is introduced into the desulfurizer 33. When passing through the first pipe 36, part of the heat of the exhaust gas is transferred to the second tank 35 via the second heat exchanger 32, and the exhaust gas is cooled. The exhaust gas introduced into the desulfurizer 33 is subjected to desulfurization treatment in the desulfurizer 33 having a cooling capacity, and after being further cooled, flows into the main path 37a of the second pipe 37. The temperature or dew point temperature of the exhaust gas that flows into the main path 37a is about 30°C, and the exhaust gas is introduced into the first tank 34 via the main path 37a and the first path 37b at about this temperature. In the first tank 34, since the temperature or dew point temperature of the exhaust gas is about 30°C, the gas absorber 38 is efficiently cooled, and as a result, carbon dioxide is efficiently absorbed, and gases other than carbon dioxide are discharged to the outside from a gas exhaust port provided in the first tank 34. The temperature or dew point temperature of the exhaust gas that flows into the main path 37a and cools the absorber does not need to be 30°C, and may be about 40°C or 50°C.

[0073] After the gas absorber 38 has absorbed carbon dioxide sufficiently, the valve of the first path 37b of the second pipe 37 is switched to a closed state, the valve of the second path 37c of the second pipe 37 is switched to an open state, the first heat exchanger 31 is switched to an ON state, and the second exchanger 32 is switched to an OFF state. As a result, the heat of the exhaust gas passing through the first pipe 36 is transferred to the first tank 34 and the gas absorber 38 via the first heat exchanger 31. In the first heat exchanger 31, it is also preferable to use water as a heat medium and heat the gas absorber 38 by introducing heated water or steam. The gas absorber 38 in the first tank 34 is heated to about 75°C by the heat from the first heat exchanger 31 and dissipates carbon dioxide. The temperature of the heated gas absorber 38 may be about 60°C or 85°C. In addition, the gas absorber 38 may be depressurized during heating. The dissipated carbon dioxide is discharged from a gas outlet provided in the first tank 34 and collected. Meanwhile, the exhaust gas at about 30°C that has flowed into the second pipe 37 via the same route as above is introduced into the second tank 35 via the second route 37c, and carbon dioxide is absorbed into the gas absorber 39 loaded in the tank 35. When the dew point temperature of the exhaust gas is lower than the temperature of the absorbing material, the absorbing material and the exhaust gas are effectively cooled by the evaporation of water from the absorbing material, which is preferable. Also, when the cooling of the absorber by the cooled exhaust gas is insufficient, it is desirable to perform additional cooling such as cooling using the latent heat of evaporation of water by introducing a cooling gas or reducing pressure or introducing a dry gas. That is, in this state, the first tank 34 functions as a stripping tower and the second tank 35 functions as an absorption tower, and the absorption and stripping of carbon dioxide gas are performed in parallel.

[0074] After the carbon dioxide is sufficiently diffused from the gas absorber 38 and absorbed into the gas absorber 39, as shown in FIG. 2, the valve of the first path 37b of the second pipe 37 is opened, the valve of the second path 37c of the second pipe 37 is closed, the first heat exchanger 31 is turned off, and the second heat exchanger 32 is turned on, so that the first tank 34 functions as an absorption tower and the second tank 35 functions as a stripping tower. As a result, the absorption and stripping of carbon dioxide gas are performed in parallel in the towers opposite to those before the switchover. Furthermore, by repeatedly performing the above-mentioned switching operation, the absorption and stripping of carbon dioxide gas from the exhaust gas can be performed continuously, and carbon dioxide gas can be efficiently separated and recovered from a large amount of exhaust gas. The number of towers filled with the gas absorber may be two or more.

[0075] As described above, in the gas recovery device of the second embodiment, the heat of the exhaust gas is reused to heat the gas absorber, and switching is performed from the state of absorbing acid gas to the state of dissipating it. Therefore, the energy utilization efficiency can be greatly improved compared to the case of using the conventional carbon dioxide gas separation and recovery process. In the second embodiment, if the temperature of the exhaust gas and the absorber cannot be controlled to a temperature suitable for absorbing and dissipating carbon dioxide, the temperature control is improved by adding a heat exchange mechanism with the outside or an additional heating mechanism to the piping and the absorber. The gas recovery device can also be used for the purpose of supplying gas, in which case it is provided as a gas supply device. EXAMPLES

[0076] The features of the present invention will be explained in more detail below with reference to examples and comparative examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be changed as appropriate without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below. In the following explanation, the concentration in parentheses indicates the concentration of the target component in the reaction mixture.

[0077] In this example, the reversible gas absorption test was carried out as follows. (CO2 reversible absorption test) The polymer sample was placed in a reactor, water was added, the reactor was sealed, and the reactor was carried into a thermostatic chamber at 30°C. 10% CO2 gas (CO2:N2=10:90) humidified at 60°C was introduced into the reactor at a flow rate of 10mL / min for 46 minutes to allow the polymer sample to absorb CO2. The temperature in the thermostatic chamber was then raised to 75°C and held for 25 minutes to allow the CO2 gas to dissipate. At this time, the amount of CO2 gas discharged from the reactor was measured and used as the amount of reversible CO2 absorption by the polymer. In the following Examples 1 to 6 and Comparative Examples 1 to 8, 20g of the polymer sample was placed in a reactor with a capacity of 90mL, and 40mL of water was added to perform the measurement.

[0078] [1] Examination of the total monomer concentration of the reaction mixture Comparative Example 1: Preparation of polymer with total monomer concentration of 1.1 mol / L N-(dimethylaminopropyl) methacrylamide (DMAPM: 5842.98 mg (6215.94 mL), 55 mol%), N,N'-methylenebisacrylamide (BIS: 962.02 mg, 10 mol%), cetyltrimethylammonium bromide (CTAB: 36.445 mg, 2 mM) were dissolved in MilliQ water to prepare a mixture with a total volume of 50 mL. This mixture was heated to 70 ° C while stirring with a mechanical stirrer, and then a solution of N-tert-butylacrylamide (TBAm: 2779.80 mg, 35 mol%) dissolved in methanol (5 mL) was added and nitrogen bubbling was performed for 30 minutes. To this mixture was added an acetone solution (250 μL) containing 2,2'-azobis(2-methylpropionitrile) (AIBN: 21.18 mg, 2.58 mM) to obtain a reaction mixture, which was polymerized at 70°C for 3 hours under a nitrogen atmosphere to obtain a polymer precipitate. This reaction solution was filtered, and the collected polymer was freeze-dried to obtain Comparative Sample 1.

[0079] Comparative Example 2: Preparation of polymer with total monomer concentration of 0.57 mol / L A polymer freeze-dried product (Comparative Sample 2) was obtained in the same manner as in Comparative Example 1, except that the amounts of DMAPM, TBAm and BIS were changed as shown in Table 1.

[0080] Example 1: Preparation of polymer with total monomer concentration of 1.7 mol / L A polymer precipitate was obtained in the same manner as in Comparative Example 1, except that the amounts of DMAPM, TBAm, and BIS were changed as shown in Table 1, and TBAm was dissolved in 8 mL of methanol and added to the mixture. 100 mL of MilliQ water was added to the polymer precipitate, and the mixture was pulverized with a hand blender to prepare a slurry. The slurry was filtered, and the collected polymer was freeze-dried to obtain Sample 1.

[0081] Example 2: Preparation of polymer with total monomer concentration of 2.4 mol / L To a flask containing BIS (4625.10 mg, 20 mol%) and CTAB (36.445 mg, 2 mM), DMAPM (14045.63 mg (14942.15 mL), 55 mol%) was added to dissolve a portion of BIS, and then 30 mL of MilliQ water was added. This mixture was heated to 70°C while stirring with a mechanical stirrer, and then a solution of TBAm (4773.00 mg, 25 mol%) dissolved in methanol (12 mL) was added, and nitrogen bubbling was performed for 30 minutes. A solution of acetone (250 μL) containing AIBN (21.18 mg, 2.58 mM) was added to this mixture to form a reaction mixture, which was polymerized at 70°C for 3 hours under a nitrogen atmosphere to obtain a polymer precipitate. This polymer precipitate was immersed in water overnight, and then the polymer was crushed with a hand mixer to obtain a slurry. The slurry was filtered, and the filtered polymer was freeze-dried to obtain sample 2.

[0082] Comparative Example 3: Preparation of polymer with total monomer concentration of 0.31 mol / L A polymer was synthesized in the same manner as in Synthesis Example 1 of WO 2016 / 024633. Specifically, 1 liter of pure water was placed in a three-neck flask and heated to 70°C, after which 2 mM of CTAB was added, and furthermore, a methanol solution containing DMAPM (55 mol%) and TBAm (43 mol%), and BIS (2 mol%) were added and dissolved so that the total monomer concentration was 0.31 mol / L. While maintaining the mixture at 70°C, the mixture was stirred with a mechanical stirrer and nitrogen bubbling was performed for 1 hour. To this mixture, 5 mL of an aqueous solution containing 2,2'-azobis(2-methylpropionamidine) dihydrochloride (700 mg) was added to obtain a reaction mixture, which was polymerized at 70°C for 3 hours under a nitrogen atmosphere to obtain polymer particles (comparative sample 3) with a particle size of 800 nm.

[0083] The amounts of components in the reaction mixtures used in the polymer synthesis for the samples produced in each Example and Comparative Example are shown in Table 1. In addition, in Comparative Sample 3 in the table below, 2,2'-azobis(2-methylpropionamidine) dihydrochloride was used as the initiator (see the * mark in the table).

[0084] [Table 1]

[0085] The results of measuring the yield and reversible CO2 absorption amount for Samples 1, 2, and Comparative Samples 1 to 3 are shown in Table 2. Here, "yield" is the ratio (%) of the actual yield to the theoretical yield of the polymer calculated from the amount of each monomer used in the reaction mixture.

[0086] [Table 2]

[0087] As shown in Table 2, samples 1 and 2 had excellent CO2 reversible absorption, with sample 2 being the best. Samples 1 and 2 also had a remarkably improved yield compared to comparative sample 3. Samples 1 and 2 and comparative samples 1 and 2 had equivalent yields. That is, sample 2, which had a higher total monomer concentration, gave a yield equivalent to sample 1 and comparative samples 1 and 2, which had lower total monomer concentrations. This shows that the yield can be increased without enlarging the production vessel, demonstrating that the production method of the present invention is industrially advantageous. In addition, when water was added to each sample to examine the water content, it was shown that the water content was lowest in the order of sample 2, 1, comparative samples 1, 2, and 3. In addition, a durability test was conducted on sample 2 in which the reversible gas absorption test was performed 50 times. The reversible CO2 absorption amount was equivalent to that of the first test even after the 50th test, confirming that the sample has sufficient durability. Furthermore, as a modification of sample 2, methanol without TBAm was added to the reaction mixture instead of the methanol solution of TBAm, and a polymer sample was produced with a DMAPM ratio of 80 mol %. A CO2 reversible absorption test was then performed, and the CO2 reversible absorption amount was increased compared to sample 2. The CO2 reversible absorption amount was also greater than that of a polymer sample prepared by adding water instead of methanol (a polymer sample produced using a 100% water solvent). As another modification of sample 2, a polymer sample was prepared using dimethylaminopropylacrylamide (DMAPAAm) instead of DMAPM as the monofunctional monomer, and the same results as those of sample 2 were obtained.

[0088] [2] Study of the concentration of multifunctional monomers and the effect of surfactants Example 3: Preparation of polymer without surfactant (CTAB) A lyophilized polymer (sample 3) was obtained in the same manner as in Example 1, except that CTAB was not added to the reaction mixture.

[0089] Comparative Example 4: Preparation of a polymer containing 10 mol % of a multifunctional polymer (BIS) A polymer freeze-dried product (Comparative Sample 4) was obtained in the same manner as in Example 3, except that, among the monomers, the ratio of TBAm was changed to 35 mol % and the ratio of BIS was changed to 10 mol %.

[0090] Comparative Example 5: Preparation of a polymer containing 10 mol % of a multifunctional polymer (EGDMA) A polymer freeze-dried product (Comparative Sample 5) was obtained in the same manner as in Example 1, except that the proportion of TBAm among the monomers was changed to 35 mol % and ethylene glycol dimethacrylate (EGDMA) was used instead of BIS at a proportion of 10 mol %.

[0091] Table 3 shows the amounts of the components in the reaction mixture used in the polymer synthesis for the samples produced in Example 3 and Comparative Examples 4 and 5. In Comparative Sample 5 in the table below, EGDMA was used as the multifunctional monomer (see the * mark in the table).

[0092] [Table 3]

[0093] When water was added to sample 1 produced in Example 1 above, sample 3 produced here, and comparative samples 4 and 5, comparative samples 4 and 5, which used 10 mol% of a multifunctional monomer (BIS or EGDMA), both had a high water content and swelled and became soft, while samples 1 and 3, which used 20 mol% of BIS, had a relatively low water content and remained hard. This shows that in order to obtain a polymer with a small degree of swelling, it is necessary to use a multifunctional monomer in a ratio of 15 mol% or more. In addition, when sample 1, which used a surfactant (CTAB), was compared with sample 3, which did not use CTAB, only sample 3 had a small amount of transparent phase near its surface. This shows that it is preferable to add a surfactant to the reaction mixture in order to obtain a uniform polymer.

[0094] Comparative Examples 6 to 8: Preparation of polymers with a ratio of multifunctional polymer (BIS) of 0 to 10 mol % and a total monomer concentration of 2.4 mol / L Among the monomers, the proportions of TBAm and BIS were changed as shown in Table 4, but the same procedure as in Example 2 was carried out to obtain lyophilized polymers (Comparative Samples 6 to 8).

[0095] Example 4: Preparation of a polymer with a proportion of multifunctional polymer (BIS) of 30 mol % and a total monomer concentration of 2.4 mol / L A lyophilized polymer (sample 4) was obtained in the same manner as in Example 2, except that the ratios of TBAm and BIS among the monomers were changed as shown in Table 4.

[0096] The amounts of the components in the reaction mixtures used in the polymer synthesis of the samples produced in Comparative Examples 6 to 8 and Example 4 are shown in Table 4, together with those of Sample 2 produced in Example 2.

[0097] [Table 4]

[0098] When water was added to the sample 2 produced in the above Example 2, the sample 4 produced here, and the comparative samples 6 to 8, the comparative sample 6, which did not use a multifunctional monomer (BIS), and the comparative samples 7 and 8, which had a BIS ratio of 5 mol% or 10 mol%, all had a high water content and swelled and became soft, but the samples 2 and 4, which had a BIS ratio of 20 mol% or 30 mol%, did not swell and remained hard. In addition, the yield and CO2 reversible absorption amount were similar for the comparative samples 7 and 8 and the samples 2 and 4 (BIS concentration: 5 to 30 mol%), but when a polymer sample with a BIS concentration of more than 30 mol% was also tested, the CO2 reversible absorption amount tended to decrease. From this, it was shown that in order to obtain a polymer with a small water content and swelling degree, it is necessary to use a multifunctional monomer at a ratio of 15 mol% or more, and in order to fully express the CO2 reversible absorption ability, it is necessary to synthesize a polymer with a multifunctional monomer at a ratio of 30 mol% or less.

[0099] Here, as a modification of sample 2, a polymer sample was produced using 20 mol% EGDMA instead of BIS as a polyfunctional monomer, and a CO2 reversible absorption test was performed. The polymer sample produced using 20 mol% EGDMA had a significantly smaller water content and swelling volume than the comparative samples with 5 mol% or 10 mol% EGDMA (approximately 1 / 3 of the case of 10 mol% EGDMA, and less than 1 / 2 of the case of 5 mol% EGDMA), and a significantly larger CO2 reversible absorption amount was obtained (approximately 1.5 times the case of 10 mol% EGDMA, and more than twice the case of 5 mol% EGDMA).

[0100] [3] Solvent considerations Examples 5 and 6: Preparation of polymer with total monomer concentration of 3.0 mol / L Polymer lyophilized products (samples 5 and 6) were obtained in the same manner as in Example 2, except that the amount of MilliQ water added to the reaction mixture and the amount of methanol used to dissolve TBAm (amount of methanol added to the reaction mixture) were changed as shown in Table 5.

[0101] The amounts of MilliQ water and methanol added to the reaction mixture in Examples 2, 5, and 6, and the reversible CO2 absorption amounts measured for Samples 2, 5, and 6 are shown in Table 5.

[0102] [Table 5]

[0103] In both Examples 5 and 6, the water content of the polymer was 0.7g (H2O) / 1g (water-containing polymer) or less, and a good polymer material with low water content was obtained. As shown in Table 5, Sample 5, which had a reduced amount of solvent, had a lower CO2 reversible absorption amount than Sample 2. Furthermore, when the solvent composition was changed to water only, the CO2 reversible absorption amount was further reduced. From this, it was found that by extremely reducing the amount of solvent, the concentration of low-polarity monomers such as TBAm in the polymer during polymerization increased, making the local environment around the amine inside the gel extremely low-polarity, and the basicity of the amine decreased, resulting in a decrease in the CO2 reversible absorption amount. It was found that even if the monomer is liquid, it is necessary to add a certain amount of water, alcohol, or other solvent to the reaction mixture. In addition, Sample 5, which used methanol, showed a larger CO2 reversible absorption amount than Sample 6, which did not use methanol, indicating that it is preferable to use an alcohol such as methanol as a solvent. In addition, polymer samples were produced and tested in the same manner as in Examples 2, 5, and 6, except that ethanol, isopropanol, butanol, or t-butanol was used instead of methanol. The results were equivalent to those obtained when methanol was used.

[0104] [4] Preparation of polymer through amine impregnation process Example 7: Preparation of a polymer using DMAm (a monofunctional monomer having no amino group) as a monofunctional monomer and carrying out an amine impregnation step Dimethylacrylamide (DMAm: 80 mol%), BIS (20 mol%) and CTAB (2 mM) were dissolved in MilliQ water to prepare a mixture with a total volume of 50 mL. Nitrogen bubbling was performed for 30 minutes while heating the mixture to 70 °C. Methanol (12 mL) that had been bubbled with nitrogen was added to the mixture, and then an acetone solution (250 μL) containing AIBN (2.58 mM) was added to form a reaction mixture, which was polymerized at 70 °C for 3 hours under a nitrogen atmosphere to obtain a polymer precipitate. The polymer precipitate was left to stand overnight in water, then crushed with a hand mixer and filtered to recover the polymer (water-containing polymer). The water content of the recovered polymer was 0.6774 g (H2O) / 1 g (water-containing polymer). 1 g of the obtained polymer was weighed out, and 2-(isopropylamino)ethanol (IPAE: 7490 μL) was added as an amine-containing treatment liquid and the polymer was immersed in the treatment liquid. The amine-containing treatment liquid was slowly stirred overnight with a shaker to replace the water contained in the polymer with 8N IPAE, and then the polymer was filtered to obtain a polymer material (sample 7) impregnated with IPAE.

[0105] Example 8: Preparation of a polymer using NiPAm (a monofunctional monomer having no amino group) as a monofunctional monomer and carrying out a step of swelling the polymer with an amine solution A polymer material (sample 8) impregnated with 8N IPAE was obtained in the same manner as in Example 7, except that N-isopropylacrylamide (NiPAm) was used instead of DMAm.

[0106] Example 9: Preparation of a polymer using DMAPM (a monofunctional monomer having an amino group) and TBAm (a monofunctional monomer having a hydrophobic group) as monofunctional monomers and carrying out a step of swelling the polymer with an amine solution The polymer obtained in the same manner as in Example 2 was left to stand overnight in water, then pulverized with a hand mixer and filtered to recover the hydrous polymer. The water in this polymer was replaced with 8N IPAE in the same manner as in Example 7 to obtain a polymer material (sample 9) impregnated with 8N IPAE.

[0107] Example 10: Preparation of a polymer using DMAPM (a monofunctional monomer having an amino group) as a monofunctional monomer and carrying out a step of swelling the polymer with an amine solution A polymer material (sample 10) impregnated with 8N IPAE was obtained in the same manner as in Example 9, except that TBAm-free methanol was added to the reaction mixture instead of the methanol solution of TBAm, and the proportion of DMAPM was 80 mol %.

[0108] For the samples produced in Examples 7 to 10, the amounts of the components in the reaction mixture used in the polymer synthesis are shown in Table 6.

[0109] [Table 6]

[0110] The CO2 reversible absorption capacity of samples 7 to 10 swollen with an amine solution was significantly increased by approximately three times for samples 7 and 8, approximately five times for sample 9, and approximately two times for sample 10, compared to the CO2 reversible absorption capacity of a polymer sample produced in the same manner except for swelling with water. It was also shown that the reversible gas absorption capacity can be further improved by improving the replacement rate of water and IPAE.

[0111] [5] Seat manufacturing (Example 11) Production of a sheet using a polymer The polymer precipitate synthesized in the same manner as in Example 2 was filtered and pulverized to obtain a polymer powder. This polymer powder and polyethylene pellets were mixed in a mass ratio of 1:2 and subjected to twin-screw extrusion molding, and the strands were spread to a width of about 4 mm with a roller and cut to about 5 mm with a pelletizer to produce a sheet of about 200 μm, width 4 mm, and length 5 mm. When a gas reversible absorption test was performed on this sheet, a CO2 reversible absorption amount of 33 mL / g was obtained. From this, it was confirmed that the produced polymer also exhibited gas reversible absorption performance as a sheet.

[0112] [6] Study on polyfunctional monomer concentration and total monomer concentration Comparative Example 9: Preparation of a polymer with a multifunctional monomer (BIS) content of 5 mol % and a total monomer concentration of 2.3 mol / L Dimethylaminopropylacrylamide (DMAPAAm: 95 mol%) and BIS (5 mol%) were dissolved in MilliQ water at 60°C to prepare a total volume of 30mL of aqueous solution, and ethanol was further added to prepare a mixture so that the total monomer concentration of the reaction mixture to be reacted in the subsequent step was 2.3 mol / L. After heating this mixture to 70°C, nitrogen bubbling was performed for 30 to 60 minutes while stirring. A solution prepared by dissolving AIBN in a mixed solvent of acetone and water (AIBN concentration in the reaction mixture: 2.58 mM) was added to this mixture to prepare a reaction mixture, which was polymerized at 70°C for 3 hours under a nitrogen stream to obtain a polymer material (Comparative Sample 9).

[0113] (Comparative Example 10, Examples 11 and 12) Preparation of polymer with a ratio of multifunctional monomer (BIS) of 10 to 30 mol % and a total monomer concentration of 2.3 mol / L Except for changing the ratio of DMAPAAm and BIS as shown in Table 7, polymer materials (Comparative Sample 10, Samples 11 and 12) were obtained in the same manner as in Comparative Example 8.

[0114] (Examples 13 to 16) Preparation of polymers with a ratio of multifunctional monomer (BIS) of 20 mol % and a total monomer concentration of 0.54 to 2.3 mol / L Polymer materials (samples 13 to 16) were obtained in the same manner as in Comparative Example 9, except that the ratio of DMAPAAm and BIS was set to DMAPAAm:BIS = 80 mol%:20 mol% and the reaction mixture was prepared so as to have the total monomer concentration shown in Table 7.

[0115] For the samples produced in Comparative Examples 9 and 10 and Examples 11 to 16, the monomer composition and total monomer concentration of the reaction mixture used in polymer synthesis, as well as the water content, swelling volume, and reversible CO2 absorption amount of the polymer material are shown in Table 7. In Table 7, "g(wet)" is the wet polymer weight, "mL(wet)" is the wet polymer volume, and "g / dry" is the dry polymer weight in g or mL.

[0116] [Table 7]

[0117] In Table 7, comparing samples 9, 10, 11, and 12 in which the total monomer concentration of the reaction mixture was set to 2.3 mol / L and the ratio of the multifunctional monomer (BIS) was changed, it can be seen that samples 11 and 12 in which the ratio of BIS was set to more than 10 mol% and 30 mol% or less had lower water content and swelling degree than samples 9 and 10 in which the ratio of BIS was set to 10 mol% or less, and the amount of CO2 reversible absorption per unit volume was improved. In addition, comparing samples 13 to 16 in which the ratio of the multifunctional monomer was set to 20 mol% and the total monomer concentration of the reaction mixture was changed, it can be seen that the higher the total monomer concentration of the reaction mixture, the lower the water content and swelling degree, and the higher the amount of CO2 reversible absorption per unit volume. From this, it was found that a material with a larger amount of CO2 reversible absorption per unit volume can be realized by setting the ratio of the multifunctional monomer within a specified range and further increasing the polymerization concentration (total monomer concentration of the reaction mixture). These materials have the advantage that they can achieve sufficient reversible CO2 absorption even when used in a relatively small volume, reducing the amount of heat required to raise temperature.

[0118] [7] Consideration of the type of initiator (Example 17) Preparation of polymer using 2,2'-azobis(2,4-dimethylvaleronitrile) (V-65) as initiator DMAPAAm (80 mol%), BIS (20 mol%) and MilliQ water were placed in a 5L separable flask (first reactor), immersed in a water bath at 50°C, and stirred. Ethanol was added to this mixture to adjust the liquid volume so that the total monomer concentration of the reaction mixture to be reacted in the subsequent step was 3 mol / L and the total volume was 3000 mL. This mixture was stirred at 100 rpm while bubbling with nitrogen for 1 hour, and then the first reactor was immersed in a water bath at 55°C. After that, the temperature of the water bath was lowered to 45°C to reduce the pressure inside the first reactor, and V-65 (2.58 mM) was added to the mixture as an initiator, and the mixture was stirred at 240 rpm for 2 minutes to prepare a reaction mixture. This reaction mixture was transferred to a stainless steel reactor (second reactor) using a tube, and the second reactor was immersed in a water bath at 55°C to react for 3 hours, and then the reaction mixture was removed from the water bath and cooled to obtain a polymer material (sample 17). The water content of sample 17 was 2.5 g (wet) / g (dry), and the reversible CO2 absorption amount was 69.5 mL / g (dry). V-65 is an initiator that starts reacting at 47℃, and by using this, it was possible to carry out the polymerization reaction at a relatively low temperature (55℃ in this case). Also, under similar conditions, it was possible to synthesize a polymer material by carrying out the polymerization reaction in a resin container (plastic bag). Furthermore, it is possible to carry out the polymerization reaction while pouring the monomer solution (mixture) onto a conveyor.

[0119] [8] Study on reversible CO2 absorption of crushed polymer materials The polymer materials synthesized in each of the above examples were pulverized using a meat chopper or a Fitzmill, and the amount of reversible CO2 absorption was measured. The results showed that the amount of reversible CO2 absorption was equivalent regardless of the pulverization method.

[0120] [9] Study of the effect of adding fine particles to polymer materials (Examples 18 and 19) Preparation of fine particle-containing polymer material A polymer material was obtained in the same manner as in Comparative Example 9, except that the ratio of DMAPAAm to BIS was DMAPAAm:BIS=85 mol %:15 mol %. The water content of this polymer material was 73.7 wt %. This polymer material was crushed in a meat chopper at 1.5th (hole diameter 4.8 mm), 1.3th (hole diameter 4.0 mm), 1st (hole diameter 3.2 mm), 7th (hole diameter 2.4 mm) and 3rd (hole diameter 1.1 mm) successively to obtain various polymer crushed products with different crushing degrees. Water-repellent silica RY300 (Evonik: AEROSIL RY300, average primary particle diameter: 7 nm, water contact angle: 100° or more) was added to each polymer crushed product in the compounding ratio shown in Table 8 to produce a fine particle-containing polymer material. The fine particle-containing polymer material was placed in a 250 mL plastic container and shaken, after which the surface was flattened and the height was measured. The results are shown in Table 8. Among these fine particle-containing polymer materials, the particle size distribution of the fine particle-containing polymer material with a water-repellent silica RY300 ratio of 0.50% by volume is shown in Figure 3, and the amount of CO2 absorbed during the absorption process and the amount of CO2 emitted during the emission process measured by the pressure swing absorption method for the fine particle-containing polymer material (sample 18) in which water-repellent silica RY300 (0.50% by volume) was added to the polymer pulverized at the 7th rin and the polymer pulverized at the 7th rin (sample 19). In Figures 3 and 4, "3rd rin polymer" to "1.5th rin polymer" respectively represent the polymer pulverized at the 3rd rin to 1.5th rin, and "RY300" represents the water-repellent silica RY300. The evaluation of reversible CO2 absorption performance using the pressure swing absorption method was carried out as follows. First, the measurement sample (10 L) contained in the reactor was placed in a thermostatic chamber at a temperature of 40 ° C and a relative humidity of over 98% to sufficiently humidify it, and then the temperature was adjusted to 30 ° C. Next, a mixed gas of humidified CO2 and N2 (CO2 concentration: 10.03% by volume) was introduced into the measurement sample at a flow rate of 1000 mL / min, and the CO2 concentration (A) of the gas discharged from the measurement sample was measured with a multi-gas analyzer (Horiba, Ltd.: VA-3000) (absorption process). Next, the gas introduced into the measurement sample was switched to humidified N2 gas, which was introduced into the measurement sample at a flow rate of 1000 mL / min, and the CO2 concentration (B) of the gas discharged from the measurement sample was measured (emission process). The CO2 reversible absorption performance of the sample was evaluated by taking the integrated value of the difference between the CO2 concentration of the introduced mixed gas and the CO2 concentration (A) measured during the absorption process as the CO2 absorption amount, and the integrated value of the CO2 concentration (B) measured during the emission process as the CO2 emission amount. When the CO2 absorption amount measured here is shown on a graph, the value is sometimes marked with a "-" sign and shown on the negative side of the vertical axis to distinguish it from the CO2 emission amount.

[0121] [Table 8]

[0122] As shown in Table 8, the bulk (loading amount) of the polymer material changed by changing the proportion of water-repellent silica RY300, with the bulk being smallest (largest loading amount) when the water-repellent silica RY300 was 0.50 vol%. Also, as shown in Figure 4, the microparticle-containing polymer material with this large loading amount (sample 18) had significantly improved CO2 reversible absorption amount and CO2 absorption / desorption rate per unit mass compared to the polymer pulverized material (sample 19) that did not contain water-repellent silica RY300. This shows that by adding microparticles, the loading amount of the polymer material can be increased, thereby improving the reversible CO2 absorption amount and the CO2 absorption / desorption rate.

[0123]

[10] Study on the effect of grinding polymer materials containing fine particles (Example 20) Production of finely divided polymer powder comprising finely divided polymer material further pulverized Among the polymer pulverized products prepared in Example 18, the pulverized product at the 1.5th minute of the meat chopper was mixed with water-repellent silica RY300 in a volume ratio of polymer pulverized product:water-repellent silica RY300=99.5:0.5 to obtain a fine particle-containing polymer material. This fine particle-containing polymer material was pulverized at 230 rpm using a planetary ball mill (Fritsch: P-5) with zirconia beads having a diameter of 5 mm to obtain a fine particle-containing polymer material pulverized product (fine particle-containing polymer pulverized product, sample 20). When the particle size distribution of sample 20 was measured, it was confirmed that the majority of the pulverized product had a particle size of less than 100 μm. In addition, the moisture content of sample 20 was 72.45% by weight, and the moisture content of the polymer pulverized product contained in sample 19 was 73.17% by weight, which was slightly lower than the moisture content (73.7% by weight) of the polymer material used as the material.

[0124] The amount of CO2 absorbed during the absorption process measured by the pressure swing absorption method for sample 20 and the above sample 19 is shown in Figure 5. Here, 10 L of the gas absorption material was used as the measurement sample, and the flow rate of the CO2 and N2 mixed gas and N2 gas was set to 3000 mL / min. From Figure 5, it can be seen that the microparticle-containing polymer pulverized with a bead mill (sample 20) has a dramatically improved CO2 absorption rate compared to the microparticle-containing polymer material not pulverized with a bead mill (sample 18). This shows that by increasing the degree of pulverization of the microparticle-containing polymer material, its reversible CO2 absorption performance can be improved.

[0125] The structures of the monomers, surfactants and initiators used in this example are shown below.

[0126] [ka] JPEG2025028892000011.jpg93159 [Industrial Applicability]

[0127] According to the manufacturing method of the present invention, a polymer having a low water content and a large reversible gas absorption capacity can be efficiently manufactured. Therefore, by using the polymer of the present invention, a gas absorbing material having a high reversible CO2 absorption capacity and good handling ability can be provided at a low cost. Therefore, the present invention has a high industrial applicability. [Explanation of symbols]

[0128] 21 Heat exchanger 22, 33 Desulfurizer 23 Gas absorber 24 No. 1 Pipe 25 No. 2 Pipe 26 3rd Pipe 26a Circulation Route 26b Branching Route 31 1st heat exchanger 32 Second heat exchanger 34 First Tank 35 Second Tank 36 No. 1 Pipe 37 No. 2 Pipe 37a Main Route 37b 1st Route 37c 2nd Route 38, 39 Gas absorber

Claims

1. An amine-containing polymeric material comprising a polymer of a monomer mixture consisting of a monofunctional monomer and greater than 10 mol % and up to 30 mol % of a multifunctional monomer.

2. The polymeric material of claim 1 , wherein the monofunctional monomer comprises an amino group.

3. The polymeric material according to claim 1 or 2, wherein the polyfunctional monomer is N,N'-alkylenebis(meth)acrylamide.

4. The polymer material according to claim 1 or 2, wherein the polyfunctional monomer has an amino group.

5. The polymeric material according to claim 1 or 2, wherein the polyfunctional monomer has a plurality of amino groups.

6. The polymeric material according to any one of claims 1 to 5, comprising a surfactant.

7. The polymeric material according to any one of claims 1 to 6, wherein the monomer mixture comprises a monomer having a hydrophobic group.

8. The polymeric material according to any one of claims 1 to 7, which is a polymeric material for gas absorption.

9. The polymeric material according to any one of claims 1 to 8, wherein when 1 gram of dry polymer is immersed in water at 30°C overnight, the water content of said polymer is 3 grams or less.

10. A polymer synthesis step of synthesizing a polymer by polymerizing monomers in a reaction mixture including a monofunctional monomer, a polyfunctional monomer, a solvent, and an initiator; an amine impregnation step of impregnating the polymer with a treatment liquid containing an amine, the total monomer concentration of the reaction mixture is 0.7 mol / L or more; The proportion of the polyfunctional monomer in the monomers contained in the reaction mixture is more than 10 mol % and 30 mol % or less, In the case where the monofunctional monomer has an amino group, the amine impregnation step does not need to be carried out.

11. The method for producing a polymer material according to claim 10, wherein the monofunctional monomer has an amino group, and the amine impregnation step is performed.

12. The method for producing a polymer material according to claim 10, wherein the monofunctional monomer has an amino group and the amine impregnation step is not performed.

13. The method for producing a polymeric material according to any one of claims 10 to 12, wherein the reaction mixture comprises a surfactant.

14. The method for producing a polymer material according to any one of claims 10 to 13, further comprising pulverizing the polymer obtained in the polymer synthesis step.

15. The method for producing a polymer material according to any one of claims 10 to 14, further comprising filtering the polymer obtained in the polymer synthesis step.

16. The method for producing a polymer material according to any one of claims 10 to 15, further comprising drying the polymer obtained in the polymer synthesis step.

17. The method for producing a polymer material according to any one of claims 10 to 16, wherein water and an alcohol are used as the solvent.

18. The method for producing a polymeric material according to any one of claims 10 to 17, comprising comprising in the reaction mixture a monomer having a hydrophobic group.

19. The method for producing a polymer material according to claim 18, further comprising, prior to the polymer synthesis step, a step of heating a mixture containing a monomer having an amino group, a polyfunctional monomer and water, and then adding a monomer having a hydrophobic group to the mixture.

20. The method for producing a polymeric material according to claim 19, wherein the monomer having a hydrophobic group is added in the form of an alcohol solution.

21. The method for producing a polymeric material according to any one of claims 18 to 20, wherein the total monomer concentration of the reaction mixture is 3 mol / L or less.

22. A polymeric material produced by the method according to any one of claims 10 to 21.

23. A gas absorbing material comprising the polymeric material according to any one of claims 1 to 9 and claim 22.

24. 24. The gas absorbing material of claim 23, further comprising a filler.

25. 25. The gas absorbing material of claim 24, wherein the filler is a powder.

26. 26. The gas absorbing material according to claim 24 or 25, wherein the filler is a fine particle having a primary particle size of 1000 nm or less.

27. 27. The gas absorbing material of claim 26, wherein the microparticles have a water contact angle of 70° or more.

28. A gas absorbing material according to any one of claims 24 to 27, wherein the filler is fumed silica.

29. The gas absorbing material according to any one of claims 24 to 27, wherein the filler is water repellent treated fumed silica.

30. A gas absorbing cartridge filled with the gas absorbing material according to any one of claims 23 to 29.

31. A gas supply device comprising a gas absorbing material according to any one of claims 23 to 29.

32. A gas recovery device comprising a gas absorbing material according to any one of claims 23 to 29.

Citation Information

Patent Citations

  • Organic amino supported metallic organic framework-porous polymer composite material as well as preparation method and application thereof

    CN108786755A

  • Acid gas absorber and air cleaner containing it

    JP2007190529A

  • Co2 absorber and method of manufacturing the same

    JP2012179584A

  • Polymer membrane, production method of the same and separation method of carbon dioxide

    JP2017159288A

  • Regenerable solid imine sorbents

    US20100292072A1